Polarizing plate with retardation layer and image display device using the same

JP7638991B2Active Publication Date: 2025-03-04NITTO DENKO CORP
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2022531848
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-08-06
Filing Date
2021-06-16
Publication Date
2025-03-04
Estimated Expiration
2041-06-16

AI Technical Summary

Benefits of technology

【0007】 本発明によれば、単体透過率とポリビニルアルコール(PVA)の複屈折またはPVA系樹脂フィルムの面内位相差とが所定の関係を満たす偏光子と、厚み10μm以下の保護層と、液晶配向化合物の配向固化層の位相差層とを有する位相差層付偏光板が提供される。このような位相差層付偏光板とすることにより、位相差層付偏光板を薄型化し、かつ、加熱時のクラック発生が抑制され得る。さらに、折り曲げ時のクラック発生をも抑制し得る。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007638991000008
    Figure 0007638991000008
  • Figure 0007638991000009
    Figure 0007638991000009
  • Figure 0007638991000010
    Figure 0007638991000010
Patent Text Reader

Abstract

Provided is a retardation-layer-equipped polarizing plate in which the occurrence of cracking during heating is suppressed. The retardation-layer-equipped polarizing plate according to the present invention comprises: a polarizing plate including a polarizer made of a polyvinyl alcohol-based resin film containing a dichroic substance, and a protective layer arranged on one side of the polarizer; and a retardation layer. This retardation layer is an orientation-solidified layer of a liquid crystal compound, and the thickness of the protective layer is 10 μm or less. In one embodiment, the following equation (1) is satisfied when the single transmittance of the polarizer is x% and the birefringence of the polyvinyl alcohol-based resin is y. In one embodiment, the following equation (2) is satisfied when the single transmittance of the polarizer is x% and the in-plane phase difference of the polyvinyl alcohol-based resin film is z nm. In one embodiment, the following equation (3) is satisfied when the single transmittance of the polarizer is x% and the orientation function of the polyvinyl alcohol-based resin is f. y < -0.011x + 0.525 (1) z < -60x + 2875 (2) f < -0.018x + 1.11 (3)
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polarizing plate with a retardation layer, and an image display device using the same. [Background technology]

[0002] In recent years, image display devices, such as liquid crystal display devices and electroluminescence (EL) display devices (for example, organic EL display devices and inorganic EL display devices), have rapidly become widespread. A polarizing plate and a retardation plate are typically used in image display devices. In practice, a retardation layer-attached polarizing plate in which a polarizing plate and a retardation plate are integrated is widely used (for example, Patent Document 1). Recently, as the demand for thinner image display devices increases, the demand for thinner retardation layer-attached polarizing plates has also increased. In addition, in recent years, there has been an increasing demand for curved image display devices and / or image display devices that can be bent or folded. Therefore, there is a demand for thinner and more flexible polarizing plates and retardation layer-attached polarizing plates.

[0003] As a method for making the polarizing plate thinner, it has been proposed to make the protective layer thinner and to laminate a protective layer only on one side of the polarizer. However, these methods cannot sufficiently protect the polarizer, and there is room for improvement in durability. Furthermore, there is a problem that cracks are likely to occur not only in the polarizer but also in the polarizing plate due to heat treatment. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2001-343521 A Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made to solve the above-mentioned problems in the prior art, and a main object of the present invention is to provide a polarizing plate with a retardation layer in which the occurrence of cracks during heating is suppressed. [Means for solving the problem]

[0006] The polarizing plate with a retardation layer according to the embodiment of the present invention includes a polarizer made of a polyvinyl alcohol-based resin film containing a dichroic material, a polarizing plate including a protective layer arranged on one side of the polarizer, and a retardation layer. The retardation layer is an alignment solidified layer of a liquid crystal compound, and the thickness of the protective layer is 10 μm or less. When the single transmittance of the polarizer is x% and the birefringence of the polyvinyl alcohol-based resin is y, the polarizer satisfies the following formula (1). y<-0.011x+0.525 (1) A polarizing plate with a retardation layer according to another embodiment of the present invention includes a polarizer made of a polyvinyl alcohol-based resin film containing a dichroic material, a polarizing plate including a protective layer arranged on one side of the polarizer, and a retardation layer. The retardation layer is an orientation-solidified layer of a liquid crystal compound, and the thickness of the protective layer is 10 μm or less. When the single transmittance of the polarizer is x% and the in-plane retardation of the polyvinyl alcohol-based resin film is z nm, the polarizer satisfies the following formula (2). z<-60x+2875 (2) A polarizing plate with a retardation layer according to yet another embodiment of the present invention includes a polarizer made of a polyvinyl alcohol-based resin film containing a dichroic material, a polarizing plate including a protective layer disposed on one side of the polarizer, and a retardation layer. The retardation layer is an orientation-solidified layer of a liquid crystal compound, and the thickness of the protective layer is 10 μm or less. When the single transmittance of the polarizer is x% and the orientation function of the polyvinyl alcohol-based resin is f, the polarizer satisfies the following formula (3). f<-0.018x+1.11 (3) In one embodiment, the retardation layer-attached polarizing plate has a total thickness of 30 μm or less. In one embodiment, the polarizer has a thickness of 10 μm or less. In one embodiment, the polarizer has a single transmittance of 40.0% or more and a polarization degree of 99.0% or more. In one embodiment, the protective layer is composed of at least one selected from the group consisting of a solidified coating film of a solution of a thermoplastic (meth)acrylic resin in an organic solvent, a photocationically cured epoxy resin, and a solidified coating film of a solution of an epoxy resin in an organic solvent. In one embodiment, the thermoplastic (meth)acrylic resin has at least one repeating unit selected from the group consisting of a lactone ring unit, a glutaric anhydride unit, a glutarimide unit, a maleic anhydride unit, and a maleimide unit. In one embodiment, the protective layer is a photocationically cured product of an epoxy resin having at least one selected from the group consisting of an aromatic skeleton and a hydrogenated aromatic skeleton. In another aspect of the present invention, there is provided an image display device, the image display device including the above-mentioned retardation layer-attached polarizing plate. Effect of the Invention

[0007] According to the present invention, a retardation layer-attached polarizing plate is provided, which has a polarizer in which the single transmittance and the birefringence of polyvinyl alcohol (PVA) or the in-plane retardation of a PVA-based resin film satisfy a predetermined relationship, a protective layer having a thickness of 10 μm or less, and a retardation layer of an orientation-solidified layer of a liquid crystal alignment compound. By making such a retardation layer-attached polarizing plate, the retardation layer-attached polarizing plate can be made thin and cracks caused during heating can be suppressed. Furthermore, cracks caused during bending can also be suppressed. [Brief description of the drawings]

[0008] [Figure 1] 1 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to another embodiment of the present invention. [Diagram 3] FIG. 11 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to still another embodiment of the present invention. [Figure 4]FIG. 2 is a schematic diagram showing an example of a drying shrinkage treatment using a heating roll in a manufacturing method of a polarizer used in the retardation layer-attached polarizing plate of the present invention.

[0009] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0010] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re(λ)=(nx-ny)×d, where d(nm) is the thickness of the layer (film). (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction measured with light of wavelength λ nm at 23° C. For example, "Rth(550)" is the retardation in the thickness direction measured with light of wavelength 550 nm at 23° C. Rth(λ) is calculated by the formula: Rth(λ)=(nx-nz)×d, where d(nm) is the thickness of the layer (film). (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When angles are referred to herein, the angles include both clockwise and counterclockwise angles relative to a reference direction, so for example, "45°" means ±45°.

[0011] A. Overall structure of the polarizing plate with a retardation layer FIG. 1 is a schematic cross-sectional view of a polarizing plate with a retardation layer according to one embodiment of the present invention. The polarizing plate with a retardation layer 100 of this embodiment has a polarizing plate 10 and a retardation layer 20. The polarizing plate 10 includes a polarizer 11, a first protective layer 12 arranged on one side of the polarizer 11, and a second protective layer 13 arranged on the other side of the polarizer 11. Depending on the purpose, one of the first protective layer 12 and the second protective layer 13 may be omitted. For example, when the retardation layer 20 can also function as a protective layer for the polarizer 11, the second protective layer 13 may be omitted. The retardation layer 20 is laminated to the polarizer 11 or the second protective layer 13 via any appropriate adhesive layer or adhesive layer (not shown). In an embodiment of the present invention, the polarizer 11 is composed of a polyvinyl alcohol-based resin film containing a dichroic material, and satisfies the following formula (1) when the single transmittance is x% and the birefringence of the polyvinyl alcohol-based resin is y. In one embodiment of the present invention, the polarizer 11 is composed of a polyvinyl alcohol-based resin film containing a dichroic material, and satisfies the following formula (2) when the single transmittance is x% and the in-plane retardation of the polyvinyl alcohol-based resin film is z nm. In one embodiment, the polarizer 10 satisfies the following formula (3) when the single transmittance is x% and the orientation function of the polyvinyl alcohol-based resin constituting the polarizer is f. y<-0.011x+0.525 (1) z<-60x+2875 (2) f< -0.018x+1.11 (3)

[0012] FIG. 2 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to another embodiment of the present invention. As shown in FIG. 2, in the retardation layer-attached polarizing plate 101 according to another embodiment, another retardation layer 50 and / or a conductive layer or a conductive layer-attached isotropic substrate 60 may be provided. The other retardation layer 50 and the conductive layer or the conductive layer-attached isotropic substrate 60 are typically provided on the outside of the retardation layer 20 (opposite the polarizing plate 10). The other retardation layer typically exhibits a relationship of refractive index characteristics of nz>nx=ny. The other retardation layer 50 and the conductive layer or the conductive layer-attached isotropic substrate 60 are typically provided in this order from the retardation layer 20 side. The other retardation layer 50 and the conductive layer or the conductive layer-attached isotropic substrate 60 are typically any layers provided as necessary, and either one or both may be omitted. For convenience, the retardation layer 20 may be referred to as a first retardation layer, and the other retardation layer 50 may be referred to as a second retardation layer. In addition, when a conductive layer or an isotropic substrate with a conductive layer is provided, the polarizing plate with a retardation layer can be applied to a so-called inner touch panel type input display device in which a touch sensor is incorporated between an image display cell (e.g., an organic EL cell) and a polarizing plate.

[0013] 3 is a schematic cross-sectional view of a polarizing plate with a retardation layer according to yet another embodiment of the present invention. In the embodiment of the present invention, the first retardation layer 20 is a layer of a liquid crystal compound with a fixed alignment. The first retardation layer 20 may be a single layer of a fixed alignment layer as shown in FIG. 1 and FIG. 2, or may have a laminated structure of a first fixed alignment layer 21 and a second fixed alignment layer 22 as shown in FIG. 3.

[0014] The above-mentioned embodiments may be appropriately combined, and the components in the above-mentioned embodiments may be modified as would be obvious in the art. For example, the retardation layer-attached polarizing plate 102 in FIG. 3 may further include a second retardation layer 50 and / or a conductive layer or a conductive layer-attached isotropic base material 60. For example, the configuration in which the conductive layer-attached isotropic base material 60 is provided on the outside of the second retardation layer 50 may be replaced with an optically equivalent configuration (for example, a laminate of the second retardation layer and a conductive layer).

[0015] The polarizing plate with a retardation layer according to the embodiment of the present invention may further include other retardation layers. The optical properties (e.g., refractive index properties, in-plane retardation, Nz coefficient, photoelastic coefficient), thickness, arrangement position, etc. of the other retardation layers can be appropriately set according to the purpose.

[0016] The polarizing plate with a retardation layer of the present invention may be in the form of a sheet or a long sheet. In this specification, the term "long sheet" means a long and narrow shape whose length is sufficiently long relative to its width, and includes, for example, a long and narrow shape whose length is 10 times or more, preferably 20 times or more, relative to its width. The long polarizing plate with a retardation layer can be wound into a roll.

[0017] For practical purposes, a pressure-sensitive adhesive layer (not shown) is provided on the opposite side of the retardation layer from the polarizing plate, so that the retardation layer-attached polarizing plate can be attached to an image display cell. Furthermore, it is preferable that a release film is temporarily attached to the surface of the pressure-sensitive adhesive layer until the retardation layer-attached polarizing plate is used. By temporarily attaching the release film, the pressure-sensitive adhesive layer is protected and roll formation is possible.

[0018] The total thickness of the retardation layer-attached polarizing plate is preferably 30 μm or less, more preferably 25 μm or less, and further preferably 20 μm or less. The total thickness may be, for example, 10 μm or more. According to the embodiment of the present invention, such an extremely thin retardation layer-attached polarizing plate can be realized. Furthermore, the occurrence of cracks during heating can also be suppressed. Such a retardation layer-attached polarizing plate can have extremely excellent flexibility and bending durability. Such a retardation layer-attached polarizing plate can be particularly suitably applied to a curved image display device and / or a bendable or foldable image display device. The total thickness of the retardation layer-attached polarizing plate refers to the sum of the thicknesses of all layers constituting the retardation layer-attached polarizing plate, excluding the adhesive layer for adhering the polarizing plate to an external adherend such as a panel or glass (i.e., the total thickness of the retardation layer-attached polarizing plate does not include the thickness of the adhesive layer for attaching the retardation layer-attached polarizing plate to an adjacent member such as an image display cell and the thickness of the release film that can be temporarily attached to the surface of the adhesive layer).

[0019] The unit weight of the retardation layer-attached polarizing plate according to the embodiment of the present invention is, for example, 6.5 mg / cm 2 or less, preferably 2.0 mg / cm 2 ~6.0mg / cm 2 and more preferably 3.0 mg / cm 2 ~5.5mg / cm 2 , and more preferably 3.5 mg / cm 2 ~5.0mg / cm 2 When the display panel is thin, the weight of the polarizing plate with a retardation layer may cause the panel to deform slightly, resulting in display defects. 2 The retardation layer-attached polarizing plate having the following unit weight can prevent such deformation of the panel. The retardation layer-attached polarizing plate having the above unit weight has good handleability even when it is thinned, and can exhibit extremely excellent flexibility and bending durability.

[0020] The components of the retardation layer-attached polarizing plate will be described in more detail below.

[0021] B. Polarizing plate B-1.Polarizer A polarizing film according to one embodiment of the present invention is made of a PVA-based resin film containing a dichroic material, and satisfies the following formula (1) when the single transmittance is x% and the birefringence of the PVA-based resin is y. A polarizing film according to another embodiment of the present invention is made of a PVA-based resin film containing a dichroic material, and satisfies the following formula (2) when the single transmittance is x% and the in-plane retardation of the PVA-based resin film is z nm. In one embodiment, a polarizer satisfies the following formula (3) when the single transmittance is x% and the orientation function of the polyvinyl alcohol-based resin constituting the polarizer is f. y<-0.011x+0.525 (1) z<-60x+2875 (2) f<-0.018x+1.11 (3)

[0022] The birefringence of the PVA resin in the polarizer (hereinafter referred to as the birefringence of PVA or Δn of PVA) and the in-plane retardation of the PVA resin film (hereinafter referred to as the "in-plane retardation of PVA") are both values ​​related to the degree of orientation of the molecular chains of the PVA resin constituting the polarizer, and can become large with an increase in the degree of orientation. The above polarizer is suppressed from breaking along the absorption axis direction due to the fact that the molecular chains of the PVA resin are more gently oriented in the absorption axis direction than in conventional polarizers. As a result, a polarizer (and thus a polarizing plate) with very excellent flexibility can be obtained. Such a polarizer (and thus a polarizing plate) can be preferably applied to a curved image display device, more preferably a bendable image display device, and even more preferably a foldable image display device. In the past, it was difficult to obtain acceptable optical properties (typically, single transmittance and degree of polarization) with a polarizer having a low degree of orientation. However, a polarizer satisfying the above formula (1) and / or formula (2) can achieve both a lower degree of orientation of the PVA-based resin than in the past and acceptable optical properties.

[0023] The polarizer according to the embodiments of the present invention preferably satisfies the following formula (1a) and / or formula (2a), and more preferably satisfies the following formula (1b) and / or formula (2b). The polarizer preferably satisfies the following formula (1a) and / or formula (2a), and more preferably satisfies the following formula (1b) and / or formula (2b). -0.004x+0.18< y < -0.011x+0.525 (1a) -0.003x+0.145< y < -0.011x+0.520 (1b) -40x+1800< z < -60x+2875 (2a) -30x+1450< z < -60x+2850 (2b)

[0024] In this specification, the in-plane retardation of the PVA is the in-plane retardation value of the PVA-based resin film at 23°C and a wavelength of 1000 nm. By using the near-infrared region as the measurement wavelength, it is possible to eliminate the influence of iodine absorption in the polarizer and to measure the retardation. In addition, the birefringence (in-plane birefringence) of the PVA is the value obtained by dividing the in-plane retardation of the PVA by the thickness of the polarizer.

[0025] The in-plane retardation of PVA is evaluated as follows: First, the retardation value is measured at multiple wavelengths of 850 nm or more, and the measured retardation value: R(λ) is plotted against the wavelength: λ, and this is fitted to the Sellmeier equation below by the least squares method. Here, A and B are fitting parameters and are coefficients determined by the least squares method. R(λ)=A+B / (λ 2 -600 2 ) In this case, the retardation value R(λ) can be separated into an in-plane retardation value (Rpva) of PVA that has no wavelength dependency and an in-plane retardation value (Ri) of iodine that has strong wavelength dependency, as shown below. Rpva= A Ri = B / (λ 2 -600 2 ) Based on this separation formula, the in-plane retardation (i.e., Rpva) of PVA at a wavelength λ=1000 nm can be calculated. The method for evaluating the in-plane retardation of PVA is also described in Japanese Patent No. 5932760, and can be referred to as necessary. In addition, the birefringence (Δn) of the PVA can be calculated by dividing this retardation by the thickness.

[0026] Commercially available devices for measuring the in-plane retardation of PVA at a wavelength of 1000 nm include the KOBRA-WR / IR series and KOBRA-31X / IR series manufactured by Oji Instruments Co., Ltd.

[0027] The orientation function (f) of the polyvinyl alcohol resin constituting the polarizer used in the present invention preferably satisfies the following formula (3a), and more preferably satisfies the following formula (3b): If the orientation function is too small, an acceptable single-unit transmittance and / or degree of polarization may not be obtained. -0.01x+0.50 <f<-0.018x+1.11 (3a) -0.01x+0.57 <f<-0.018x+1.1 (3b)

[0028] The orientation function (f) is determined, for example, by attenuated total reflection (ATR) measurement using a Fourier transform infrared spectrophotometer (FT-IR) and polarized light as the measurement light. Specifically, germanium is used as the crystallite to which the polarizer is attached, the incident angle of the measurement light is 45°, the incident polarized infrared light (measurement light) is polarized light (s-polarized light) that vibrates parallel to the surface to which the germanium crystal sample is attached, and the measurement is performed with the stretching direction of the polarizer arranged parallel and perpendicular to the polarization direction of the measurement light. -1 The intensity I is calculated according to the following formula using the intensity of 3330 cm -1 is used as the reference peak, and 2941 cm -1 / 3330cm -1 The value is 2941 cm. Note that f=1 is perfect alignment, and f=0 is random. -1 The peak is considered to be an absorption caused by the vibration of the main chain (-CH2-) of PVA in the polarizer. f=(3 <cos 2 θ>-1) / 2 =(1-D) / [c(2D+1)] =-2×(1-D) / (2D+1) however, c = (3cos 2 β-1) / 2, 2941cm -1 For vibration, β=90°. θ: Angle of molecular chain to stretching direction β: Angle of the transition dipole moment with respect to the chain axis D=(I⊥ ) / (I / / ) (In this case, the more the PVA molecules are oriented, the larger D becomes.) I ⊥ : Absorption intensity when the polarization direction of the measurement light and the stretching direction of the polarizer are perpendicular I / / : Absorption intensity when the polarization direction of the measurement light and the stretching direction of the polarizer are parallel

[0029] The thickness of the polarizer is preferably 10 μm or less, more preferably 8 μm or less. The lower limit of the thickness of the polarizer may be, for example, 1 μm. The thickness of the polarizer may be 2 μm to 10 μm in one embodiment, and 2 μm to 8 μm in another embodiment. By making the thickness of the polarizer so thin, it is possible to make the thermal shrinkage very small. It is presumed that such a configuration may also contribute to suppressing breakage in the absorption axis direction.

[0030] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is preferably 40.0% or more, more preferably 41.0% or more. The upper limit of the single transmittance may be, for example, 49.0%. In one embodiment, the single transmittance of the polarizer is 40.0% to 45.0%. The degree of polarization of the polarizer is preferably 99.0% or more, more preferably 99.4% or more. The upper limit of the degree of polarization may be, for example, 99.999%. In one embodiment, the degree of polarization of the polarizer is 99.0% to 99.99%. One feature of the polarizer according to the embodiment of the present invention is that the degree of orientation of the PVA-based resin constituting the polarizer is lower than that of a conventional polarizer, and the polarizer has the above-mentioned in-plane retardation, birefringence, and / or orientation function, yet the polarizer can achieve such a single transmittance and degree of polarization that are practically acceptable. This is presumably due to the manufacturing method described later. The single transmittance is typically a Y value measured using an ultraviolet-visible spectrophotometer and subjected to luminosity correction. The polarization degree is typically calculated by the following formula based on the parallel transmittance Tp and the crossed transmittance Tc measured using an ultraviolet-visible spectrophotometer and subjected to luminosity correction. Degree of polarization (%)={(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100

[0031] The piercing strength of the polarizer is, for example, 30 gf / μm or more, preferably 35 gf / μm or more, more preferably 40 gf / μm or more, even more preferably 45 gf / μm or more, and particularly preferably 50 gf / μm or more. The piercing strength can be, for example, 80 gf / μm or less. By setting the piercing strength of the polarizer in such a range, it is possible to significantly suppress the polarizer from being torn along the absorption axis direction. As a result, a polarizer (and, as a result, a polarizing plate) with very excellent flexibility can be obtained. The piercing strength indicates the crack resistance of the polarizer when the polarizer is pierced with a predetermined strength. The piercing strength can be expressed, for example, as the strength (breaking strength) at which the polarizer breaks when a predetermined needle is attached to a compression tester and the needle is pierced into the polarizer at a predetermined speed. As is clear from the unit, the piercing strength means the piercing strength per unit thickness (1 μm) of the polarizer.

[0032] As described above, the polarizer is composed of a PVA-based resin film containing a dichroic material. Preferably, the PVA-based resin constituting the PVA-based resin film (substantially the polarizer) contains an acetoacetyl-modified PVA-based resin. With such a configuration, a polarizer having a desired piercing strength can be obtained. The blending amount of the acetoacetyl-modified PVA-based resin is preferably 5% by weight to 20% by weight, and more preferably 8% by weight to 12% by weight, when the entire PVA-based resin is taken as 100% by weight. If the blending amount is within such a range, the piercing strength can be set to a more suitable range.

[0033] A polarizer can be typically produced using a laminate of two or more layers. A specific example of a polarizer obtained using a laminate includes a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer coated on the resin substrate. A polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer coated on the resin substrate can be produced by, for example, applying a PVA-based resin solution to the resin substrate, drying the resin substrate to form a PVA-based resin layer on the resin substrate, and obtaining a laminate of the resin substrate and the PVA-based resin layer; stretching and dyeing the laminate to make the PVA-based resin layer into a polarizer. In this embodiment, a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is preferably formed on one side of the resin substrate. The stretching typically includes immersing the laminate in an aqueous boric acid solution to stretch the laminate. Furthermore, the stretching preferably further includes stretching the laminate in air at a high temperature (for example, 95° C. or higher) before stretching in the aqueous boric acid solution. In an embodiment of the present invention, the total stretching ratio is preferably 3.0 to 4.5 times, which is significantly smaller than normal. Even at such a total stretching ratio, a polarizer having acceptable optical properties can be obtained by adding a halide and combining it with a dry shrinkage treatment. Furthermore, in an embodiment of the present invention, the stretching ratio of the auxiliary air stretching is preferably larger than the stretching ratio of the boric acid water stretching. With this configuration, a polarizer having acceptable optical properties can be obtained even at a small total stretching ratio. In addition, the laminate is preferably subjected to a dry shrinkage treatment in which the laminate is heated while being transported in the longitudinal direction to shrink the laminate by 2% or more in the width direction. In one embodiment, the method for producing a polarizer includes subjecting the laminate to an auxiliary air stretching treatment, a dyeing treatment, an underwater stretching treatment, and a dry shrinkage treatment in this order. By introducing the auxiliary stretching, even when a PVA-based resin is applied onto a thermoplastic resin, it is possible to increase the crystallinity of the PVA-based resin, and to achieve high optical properties. At the same time, by increasing the orientation of the PVA-based resin in advance, problems such as a decrease in the orientation of the PVA-based resin or dissolution when the resin is immersed in water in the subsequent dyeing and stretching processes can be prevented, making it possible to achieve high optical properties.Furthermore, when the PVA-based resin layer is immersed in a liquid, the orientation of polyvinyl alcohol molecules is disturbed and the orientation is reduced, compared to when the PVA-based resin layer does not contain a halide. This can improve the optical properties of a polarizer obtained by immersing the laminate in a liquid through a treatment process such as a dyeing process and an underwater stretching process. Furthermore, the optical properties can be improved by shrinking the laminate in the width direction through a drying shrinkage process. The obtained resin substrate / polarizer laminate may be used as it is (i.e., the resin substrate may be used as a protective layer for the polarizer), or the resin substrate may be peeled off from the resin substrate / polarizer laminate and any suitable protective layer may be laminated on the peeled surface according to the purpose. Details of the method for producing a polarizing film will be described later.

[0034] B-2. Manufacturing method of polarizer A method for producing a polarizer according to one embodiment of the present invention includes forming a polyvinyl alcohol-based resin layer (PVA-based resin layer) containing a halide and a polyvinyl alcohol-based resin (PVA-based resin) on one side of a long thermoplastic resin substrate to form a laminate, and subjecting the laminate to an auxiliary air-stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in this order, in which the laminate is heated while being transported in the longitudinal direction to shrink the laminate by 1% to 10% in the width direction. The content of the halide in the PVA-based resin layer is preferably 5 parts by weight to 20 parts by weight with respect to 100 parts by weight of the PVA-based resin. The drying shrinkage treatment is preferably performed using a heating roll, and the temperature of the heating roll is preferably 60° C. to 120° C. The shrinkage rate of the laminate in the width direction due to the drying shrinkage treatment is preferably 1% to 10%. According to such a production method, the polarizer described in the above item B-1 can be obtained. In particular, a laminate including a PVA-based resin layer containing a halide is prepared, the laminate is stretched in multiple stages including auxiliary air stretching and underwater stretching, and the laminate after stretching is heated with a heating roll, whereby a polarizer having excellent optical properties (typically, single transmittance and polarization degree) can be obtained.

[0035] B-2-1. Preparation of laminate Any suitable method can be adopted as a method for producing a laminate of a thermoplastic resin substrate and a PVA-based resin layer. Preferably, a coating liquid containing a halide and a PVA-based resin is applied to the surface of the thermoplastic resin substrate, and then dried to form a PVA-based resin layer on the thermoplastic resin substrate. As described above, the content of the halide in the PVA-based resin layer is preferably 5 to 20 parts by weight relative to 100 parts by weight of the PVA-based resin.

[0036] Any appropriate method can be used as the coating method of the coating liquid. For example, roll coating, spin coating, wire bar coating, dip coating, die coating, curtain coating, spray coating, knife coating (comma coating, etc.), etc. are listed. The coating and drying temperature of the coating liquid is preferably 50° C. or higher.

[0037] The thickness of the PVA-based resin layer is preferably 2 μm to 30 μm, and more preferably 2 μm to 20 μm. By making the thickness of the PVA-based resin layer before stretching very thin in this manner and reducing the total stretching ratio as described later, a polarizer having an acceptable single transmittance and polarization degree can be obtained despite a very small orientation function.

[0038] Before forming the PVA-based resin layer, the thermoplastic resin substrate may be subjected to a surface treatment (e.g., corona treatment, etc.), or an easy-adhesion layer may be formed on the thermoplastic resin substrate. By carrying out such treatment, the adhesion between the thermoplastic resin substrate and the PVA-based resin layer can be improved.

[0039] B-2-1-1. Thermoplastic resin base material Any suitable thermoplastic resin film may be used as the thermoplastic resin substrate. Details of the thermoplastic resin substrate are described in, for example, JP 2012-73580 A and Japanese Patent No. 6470455 A. The entire disclosure of these publications is incorporated herein by reference.

[0040] B-2-1-2. Coating liquid The coating liquid contains a halide and a PVA resin as described above. The coating liquid is typically a solution in which the halide and the PVA resin are dissolved in a solvent. Examples of the solvent include water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, various glycols, polyhydric alcohols such as trimethylolpropane, and amines such as ethylenediamine and diethylenetriamine. These can be used alone or in combination of two or more. Among these, water is preferred. The concentration of the PVA resin in the solution is preferably 3 to 20 parts by weight relative to 100 parts by weight of the solvent. With such a resin concentration, a uniform coating film that is in close contact with the thermoplastic resin substrate can be formed. The content of the halide in the coating liquid is preferably 5 to 20 parts by weight relative to 100 parts by weight of the PVA resin.

[0041] Additives may be added to the coating liquid. Examples of additives include plasticizers and surfactants. Examples of plasticizers include polyhydric alcohols such as ethylene glycol and glycerin. Examples of surfactants include nonionic surfactants. These can be used to further improve the uniformity, dyeability, and stretchability of the resulting PVA-based resin layer.

[0042] Any appropriate resin may be adopted as the PVA-based resin. Examples include polyvinyl alcohol and ethylene-vinyl alcohol copolymer. Polyvinyl alcohol is obtained by saponifying polyvinyl acetate. Ethylene-vinyl alcohol copolymer is obtained by saponifying ethylene-vinyl acetate copolymer. The saponification degree of the PVA-based resin is usually 85 mol% to 100 mol%, preferably 95.0 mol% to 99.95 mol%, and more preferably 99.0 mol% to 99.93 mol%. The saponification degree can be determined in accordance with JIS K 6726-1994. By using a PVA-based resin having such a saponification degree, a polarizer having excellent durability can be obtained. If the saponification degree is too high, gelation may occur. As described above, the PVA-based resin preferably contains an acetoacetyl-modified PVA-based resin.

[0043] The average degree of polymerization of the PVA resin can be appropriately selected depending on the purpose. The average degree of polymerization is usually 1000 to 10000, preferably 1200 to 4500, and more preferably 1500 to 4300. The average degree of polymerization can be determined in accordance with JIS K 6726-1994.

[0044] Any suitable halide may be used as the halide. For example, iodide and sodium chloride may be used. For example, iodide may be potassium iodide, sodium iodide, and lithium iodide. Among these, potassium iodide is preferred.

[0045] The amount of the halide in the coating solution is preferably 5 to 20 parts by weight per 100 parts by weight of the PVA-based resin, and more preferably 10 to 15 parts by weight per 100 parts by weight of the PVA-based resin. If the amount of the halide exceeds 20 parts by weight per 100 parts by weight of the PVA-based resin, the halide may bleed out, causing the finally obtained polarizer to become cloudy.

[0046] Generally, the orientation of polyvinyl alcohol molecules in the PVA-based resin increases when the PVA-based resin layer is stretched, but when the stretched PVA-based resin layer is immersed in a liquid containing water, the orientation of the polyvinyl alcohol molecules may become disordered, and the orientation may decrease. In particular, when a laminate of a thermoplastic resin and a PVA-based resin layer is stretched in boric acid water, the tendency of the orientation degree to decrease is remarkable when the laminate is stretched in boric acid water at a relatively high temperature to stabilize the stretching of the thermoplastic resin. For example, the stretching of a PVA film alone in boric acid water is generally performed at 60°C, whereas the stretching of a laminate of A-PET (thermoplastic resin substrate) and a PVA-based resin layer is performed at a high temperature of about 70°C, and in this case, the orientation of PVA at the initial stage of stretching may decrease before it increases due to underwater stretching. In response to this, a laminate of a PVA-based resin layer containing a halide and a thermoplastic resin substrate is prepared, and the laminate is stretched at high temperature (auxiliary stretching) in air before being stretched in boric acid water, so that the crystallization of the PVA-based resin in the PVA-based resin layer of the laminate after the auxiliary stretching can be promoted. As a result, when the PVA-based resin layer is immersed in a liquid, the orientation of the polyvinyl alcohol molecules can be prevented from being disturbed and the orientation can be prevented from being reduced, compared to when the PVA-based resin layer does not contain a halide. This can improve the optical properties of a polarizer obtained by immersing the laminate in a liquid through a process such as a dyeing process and an underwater stretching process.

[0047] B-2-2. Aerial supplementary stretching process In particular, in order to obtain high optical properties, a two-stage stretching method is selected, which combines dry stretching (auxiliary stretching) and stretching in boric acid water. By introducing auxiliary stretching like two-stage stretching, it is possible to stretch while suppressing the crystallization of the thermoplastic resin substrate. Furthermore, when applying a PVA-based resin on a thermoplastic resin substrate, it is necessary to lower the application temperature compared to when applying a PVA-based resin on a normal metal drum in order to suppress the influence of the glass transition temperature of the thermoplastic resin substrate, and as a result, the crystallization of the PVA-based resin becomes relatively low, and a problem that sufficient optical properties cannot be obtained may occur. On the other hand, by introducing auxiliary stretching, it is possible to increase the crystallinity of the PVA-based resin even when applying a PVA-based resin on a thermoplastic resin, and it is possible to achieve high optical properties. At the same time, by increasing the orientation of the PVA-based resin in advance, problems such as a decrease in the orientation of the PVA-based resin or dissolution can be prevented when immersed in water in the subsequent dyeing process or stretching process, and it is possible to achieve high optical properties.

[0048] The stretching method of the auxiliary air stretching may be fixed end stretching (for example, a method of stretching using a tenter stretching machine) or free end stretching (for example, a method of uniaxially stretching a laminate between rolls having different peripheral speeds). In order to obtain high optical properties, free end stretching may be actively adopted. In one embodiment, the air stretching process includes a heated roll stretching process in which the laminate is stretched by the difference in peripheral speed between heated rolls while being transported in its longitudinal direction. The air stretching process typically includes a zone stretching process and a heated roll stretching process. The order of the zone stretching process and the heated roll stretching process is not limited, and the zone stretching process may be performed first, or the heated roll stretching process may be performed first. The zone stretching process may be omitted. In one embodiment, the zone stretching process and the heated roll stretching process are performed in this order. In another embodiment, the film is stretched by gripping the film end in a tenter stretching machine and widening the distance between the tenters in the flow direction (the widening of the distance between the tenters is the stretching ratio). At this time, the distance of the tenter in the width direction (perpendicular to the machine direction) is set to be as close as possible. Preferably, it can be set to be as close as possible to the free end stretching ratio in the machine direction. In the case of free end stretching, the shrinkage ratio in the width direction = (1 / stretching ratio) 1 / 2 It is calculated as follows.

[0049] The auxiliary air-drawing may be performed in one step or in multiple steps. When the auxiliary air-drawing is performed in multiple steps, the draw ratio is the product of the draw ratios in each step. The draw direction in the auxiliary air-drawing is preferably approximately the same as the draw direction in the underwater drawing.

[0050] The stretching ratio in the auxiliary air stretching is preferably 1.0 to 4.0 times, more preferably 1.5 to 3.5 times, and further preferably 2.0 to 3.0 times. If the stretching ratio of the auxiliary air stretching is in such a range, the total stretching ratio can be set in a desired range when combined with underwater stretching, and a desired orientation function can be realized. As a result, a polarizer in which breakage along the absorption axis direction is suppressed can be obtained. Furthermore, as described above, the stretching ratio of the auxiliary air stretching is preferably larger than the stretching ratio of the underwater stretching. With this configuration, a polarizer having acceptable optical properties can be obtained even if the total stretching ratio is small. More specifically, the ratio of the stretching ratio of the auxiliary air stretching to the stretching ratio of the underwater stretching (underwater stretching / auxiliary air stretching) is preferably 0.4 to 0.9, more preferably 0.5 to 0.8.

[0051] The stretching temperature of the auxiliary in-air stretching can be set to any appropriate value depending on the material of the thermoplastic resin substrate, the stretching method, etc. The stretching temperature is preferably equal to or higher than the glass transition temperature (Tg) of the thermoplastic resin substrate, more preferably equal to or higher than the glass transition temperature (Tg) of the thermoplastic resin substrate + 10°C, and particularly preferably equal to or higher than Tg + 15°C. On the other hand, the upper limit of the stretching temperature is preferably 170°C. By stretching at such a temperature, rapid crystallization of the PVA resin can be suppressed, and defects due to the crystallization (for example, the orientation of the PVA resin layer due to stretching is hindered) can be suppressed.

[0052] B-2-3. Insolubilization, dyeing and crosslinking treatments If necessary, after the auxiliary air stretching treatment, an insolubilization treatment is performed before the underwater stretching treatment or the dyeing treatment. The insolubilization treatment is typically performed by immersing the PVA-based resin layer in an aqueous boric acid solution. The dyeing treatment is typically performed by dyeing the PVA-based resin layer with a dichroic substance (typically iodine). If necessary, after the dyeing treatment, a crosslinking treatment is performed before the underwater stretching treatment. The crosslinking treatment is typically performed by immersing the PVA-based resin layer in an aqueous boric acid solution. Details of the insolubilization treatment, the dyeing treatment, and the crosslinking treatment are described, for example, in JP 2012-73580 A (above).

[0053] B-2-4. Underwater stretching process The underwater stretching treatment is performed by immersing the laminate in a stretching bath. According to the underwater stretching treatment, the laminate can be stretched at a temperature lower than the glass transition temperature (typically about 80° C.) of the thermoplastic resin substrate or the PVA-based resin layer, and the PVA-based resin layer can be stretched while suppressing crystallization. As a result, a polarizer having excellent optical properties can be produced.

[0054] The stretching method of the laminate can be any appropriate method. Specifically, it may be fixed end stretching or free end stretching (for example, a method of uniaxially stretching the laminate by passing it between rolls having different peripheral speeds). Preferably, free end stretching is selected. The stretching of the laminate may be performed in one stage or multiple stages. When performing multiple stages, the total stretching ratio is the product of the stretching ratios in each stage.

[0055] The underwater stretching is preferably performed by immersing the laminate in an aqueous solution of boric acid (stretching in boric acid water). By using an aqueous solution of boric acid as a stretching bath, it is possible to impart to the PVA-based resin layer rigidity that can withstand the tension applied during stretching and water resistance that does not dissolve in water. Specifically, boric acid can generate tetrahydroxyborate anions in the aqueous solution and crosslink with the PVA-based resin through hydrogen bonds. As a result, it is possible to impart rigidity and water resistance to the PVA-based resin layer and stretch it well, and to produce a polarizer with excellent optical properties.

[0056] The boric acid aqueous solution is preferably obtained by dissolving boric acid and / or a borate in water as a solvent. The boric acid concentration is preferably 1 to 10 parts by weight, more preferably 2.5 to 6 parts by weight, and particularly preferably 3 to 5 parts by weight, relative to 100 parts by weight of water. By setting the boric acid concentration to 1 part by weight or more, dissolution of the PVA-based resin layer can be effectively suppressed, and a polarizer with higher characteristics can be produced. In addition to boric acid or a borate, an aqueous solution obtained by dissolving a boron compound such as borax, glyoxal, glutaraldehyde, or the like in a solvent can also be used.

[0057] Preferably, an iodide is added to the stretching bath (boric acid aqueous solution). By adding an iodide, it is possible to suppress the elution of iodine adsorbed in the PVA resin layer. Specific examples of the iodide are as described above. The concentration of the iodide is preferably 0.05 to 15 parts by weight, more preferably 0.5 to 8 parts by weight, relative to 100 parts by weight of water.

[0058] The stretching temperature (liquid temperature of the stretching bath) is preferably 40°C to 85°C, more preferably 60°C to 75°C. At such a temperature, the laminate can be stretched at a high ratio while suppressing dissolution of the PVA-based resin layer. Specifically, as described above, the glass transition temperature (Tg) of the thermoplastic resin substrate is preferably 60°C or higher in relation to the formation of the PVA-based resin layer. In this case, if the stretching temperature is lower than 40°C, there is a risk that the substrate cannot be stretched well even when the plasticization of the thermoplastic resin substrate by water is taken into consideration. On the other hand, the higher the temperature of the stretching bath, the higher the solubility of the PVA-based resin layer, and there is a risk that excellent optical properties cannot be obtained. The immersion time of the laminate in the stretching bath is preferably 15 seconds to 5 minutes.

[0059] The stretching ratio in underwater stretching is preferably 1.0 to 3.0 times, more preferably 1.0 to 2.0 times, and further preferably 1.0 to 1.5 times. When the stretching ratio in underwater stretching is in such a range, the total stretching ratio can be set in a desired range, and a desired orientation function can be realized. As a result, a polarizer in which breakage along the absorption axis direction is suppressed can be obtained. As described above, the total stretching ratio (the total stretching ratio when the auxiliary air stretching and the underwater stretching are combined) is, for example, 3.0 to 4.5 times, preferably 3.0 to 4.0 times, and more preferably 3.0 to 3.5 times, relative to the original length of the laminate. By appropriately combining the addition of a halide to the coating solution, the adjustment of the stretching ratios of the auxiliary air stretching and the underwater stretching, and the drying shrinkage treatment, a polarizer having acceptable optical properties can be obtained even at such a total stretching ratio.

[0060] B-2-5. Drying shrinkage treatment The drying shrinkage treatment may be performed by zone heating in which the entire zone is heated, or by heating the transport roll (using a so-called heating roll) (heat roll drying method). Preferably, both are used. By drying using a heating roll, it is possible to efficiently suppress the heat curl of the laminate and produce a polarizer with excellent appearance. Specifically, by drying the laminate in a state where it is aligned with the heating roll, it is possible to efficiently promote the crystallization of the thermoplastic resin substrate and increase the crystallinity, and even at a relatively low drying temperature, it is possible to satisfactorily increase the crystallinity of the thermoplastic resin substrate. As a result, the rigidity of the thermoplastic resin substrate increases and it becomes in a state where it can withstand the shrinkage of the PVA-based resin layer due to drying, and curling is suppressed. In addition, by using a heating roll, it is possible to dry the laminate while maintaining it in a flat state, so that it is possible to suppress not only curling but also the occurrence of wrinkles. At this time, the optical properties of the laminate can be improved by shrinking it in the width direction by the drying shrinkage treatment. This is because the orientation of the PVA and the PVA / iodine complex can be effectively increased. The shrinkage rate in the width direction of the laminate due to the drying shrinkage treatment is preferably 1% to 10%, more preferably 2% to 8%, and particularly preferably 4% to 6%.

[0061] 4 is a schematic diagram showing an example of the drying shrinkage treatment. In the drying shrinkage treatment, the laminate 200 is dried while being transported by transport rolls R1 to R6 heated to a predetermined temperature and guide rolls G1 to G4. In the illustrated example, the transport rolls R1 to R6 are arranged so as to alternately and continuously heat the surface of the PVA resin layer and the surface of the thermoplastic resin substrate, but, for example, the transport rolls R1 to R6 may be arranged so as to continuously heat only one surface of the laminate 200 (for example, the thermoplastic resin substrate surface).

[0062] Drying conditions can be controlled by adjusting the heating temperature of the transport rolls (temperature of the heating rolls), the number of heating rolls, the contact time with the heating rolls, etc. The temperature of the heating rolls is preferably 60°C to 120°C, more preferably 65°C to 100°C, and particularly preferably 70°C to 80°C. The crystallinity of the thermoplastic resin can be favorably increased, curling can be favorably suppressed, and an optical laminate with extremely excellent durability can be produced. The temperature of the heating rolls can be measured by a contact thermometer. In the illustrated example, six transport rolls are provided, but there is no particular restriction as long as there are multiple transport rolls. The number of transport rolls is usually 2 to 40, preferably 4 to 30. The contact time (total contact time) between the laminate and the heating rolls is preferably 1 to 300 seconds, more preferably 1 to 20 seconds, and even more preferably 1 to 10 seconds.

[0063] The heating roll may be provided in a heating furnace (for example, an oven) or in a normal production line (under room temperature environment). It is preferably provided in a heating furnace equipped with a blowing means. By using drying with a heating roll in combination with hot air drying, it is possible to suppress abrupt temperature changes between the heating rolls, and it is possible to easily control shrinkage in the width direction. The hot air drying temperature is preferably 30°C to 100°C. The hot air drying time is preferably 1 second to 300 seconds. The hot air speed is preferably about 10 m / s to 30 m / s. The wind speed is the wind speed in the heating furnace, and can be measured by a mini-vane type digital anemometer.

[0064] B-2-6. Other processing Preferably, after the underwater stretching treatment and before the drying shrinkage treatment, a washing treatment is carried out. The washing treatment is typically carried out by immersing the PVA-based resin layer in an aqueous potassium iodide solution.

[0065] B-3.Protective layer In an embodiment of the present invention, the thickness of the protective layer is 10 μm or less. The thickness of the protective layer is 10 μm or less, which can contribute to the thinning of the polarizing plate. Even if the thickness of the protective layer of the retardation layer-attached polarizing plate is 10 μm or less, the occurrence of cracks during heating can be prevented. The thickness of the protective layer is preferably 7 μm or less, more preferably 5 μm or less, and even more preferably 3 μm or less. The thickness of the protective layer is, for example, 1 μm or more.

[0066] The protective layer may be formed of any suitable material, including cellulose-based resins such as triacetyl cellulose (TAC), transparent resins such as polyesters, polyvinyl alcohols, polycarbonates, polyamides, polyimides, polyethersulfones, polysulfones, polystyrenes, polynorbornenes, polyolefins, (meth)acrylics, and acetates, thermosetting or ultraviolet-curing resins such as (meth)acrylics, urethanes, (meth)acrylic urethanes, epoxy resins, and silicones, and glassy polymers such as siloxane polymers.

[0067] The protective layer may be a film, a solidified product of a coating film, or a cured product (e.g., a photocationically cured product). In one embodiment, the protective layer is composed of at least one selected from the group consisting of a solidified product of a coating film of an organic solvent solution of a thermoplastic (meth)acrylic resin (hereinafter, the (meth)acrylic resin may be simply referred to as an acrylic resin), a photocationically cured product of an epoxy resin, and a solidified product of a coating film of an organic solvent solution of an epoxy resin. The following is a specific description.

[0068] B-3-1.Solidified coating of organic solvent solution of thermoplastic acrylic resin In one embodiment, the protective layer is made of a solidified coating film of a solution of a thermoplastic acrylic resin in an organic solvent.

[0069] B-3-1-1. Acrylic resin The acrylic resin preferably has a glass transition temperature (Tg) of 100° C. or higher. As a result, the protective layer has a Tg of 100° C. or higher. If the acrylic resin has a Tg of 100° C. or higher, a polarizing plate including a protective layer obtained from such a resin can have excellent durability. The acrylic resin preferably has a Tg of 110° C. or higher, more preferably 115° C. or higher, even more preferably 120° C. or higher, and particularly preferably 125° C. or higher. On the other hand, the acrylic resin preferably has a Tg of 300° C. or lower, more preferably 250° C. or lower, even more preferably 200° C. or lower, and particularly preferably 160° C. or lower. If the acrylic resin has a Tg in this range, it can have excellent moldability.

[0070] As the acrylic resin, any appropriate acrylic resin may be adopted as long as it has the above Tg. The acrylic resin typically contains an alkyl(meth)acrylate as a main component as a monomer unit (repeating unit). In this specification, "(meth)acrylic" means acrylic and / or methacrylic. Examples of the alkyl(meth)acrylate constituting the main skeleton of the acrylic resin include linear or branched alkyl groups having 1 to 18 carbon atoms. These can be used alone or in combination. Furthermore, any appropriate copolymerization monomer may be introduced into the acrylic resin by copolymerization. The repeating unit derived from the alkyl(meth)acrylate is typically represented by the following general formula (1):

[0071] [ka]

[0072] In the general formula (1), R 4 represents a hydrogen atom or a methyl group, and R 5represents a hydrogen atom, or an optionally substituted aliphatic or alicyclic hydrocarbon group having 1 to 6 carbon atoms. Examples of the substituent include halogen and a hydroxyl group. Specific examples of alkyl (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, benzyl (meth)acrylate, dicyclopentanyloxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, chloromethyl (meth)acrylate, 2-chloroethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2,3,4,5,6-pentahydroxyhexyl (meth)acrylate, 2,3,4,5-tetrahydroxypentyl (meth)acrylate, methyl 2-(hydroxymethyl)acrylate, ethyl 2-(hydroxymethyl)acrylate, and methyl 2-(hydroxyethyl)acrylate. In the general formula (1), R 5 is preferably a hydrogen atom or a methyl group. Thus, a particularly preferred alkyl (meth)acrylate is methyl acrylate or methyl methacrylate.

[0073] The acrylic resin may contain only a single alkyl (meth)acrylate unit, or may be a single alkyl (meth)acrylate unit represented by the general formula (1) above. 4 and R 5 It may contain a plurality of alkyl (meth)acrylate units having different structures.

[0074] The content of alkyl (meth)acrylate units in the acrylic resin is preferably 50 mol% to 98 mol%, more preferably 55 mol% to 98 mol%, even more preferably 60 mol% to 98 mol%, particularly preferably 65 mol% to 98 mol%, and most preferably 70 mol% to 97 mol%. If the content is less than 50 mol%, the effects derived from the alkyl (meth)acrylate units (e.g., high heat resistance, high transparency) may not be fully exhibited. If the content is more than 98 mol%, the resin may become brittle and easily cracked, and high mechanical strength may not be fully exhibited, resulting in poor productivity.

[0075] The acrylic resin preferably has a repeating unit containing a ring structure. Examples of the repeating unit containing a ring structure include a lactone ring unit, a glutaric anhydride unit, a glutarimide unit, a maleic anhydride unit, and a maleimide (N-substituted maleimide) unit. The repeating unit containing a ring structure may contain only one type of repeating unit, or may contain two or more types of repeating units.

[0076] The lactone ring unit is preferably represented by the following general formula (2):

[0077] [ka] In the general formula (2), R 1 , R 2 and R 3 each independently represents a hydrogen atom or an organic residue having 1 to 20 carbon atoms. The organic residue may contain an oxygen atom. The acrylic resin may contain only a single lactone ring unit, and R 1 , R 2 and R 3 The acrylic resin may contain a plurality of lactone ring units having different ring structures. Acrylic resins having lactone ring units are described in, for example, JP-A-2008-181078, the disclosure of which is incorporated herein by reference.

[0078] The glutarimide unit is preferably represented by the following general formula (3):

[0079] [ka]

[0080] In the general formula (3), R 11 and R 12 each independently represents a hydrogen atom or an alkyl group having 1 to 8 carbon atoms; R 13 represents an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an aryl group having 6 to 10 carbon atoms. 11 and R 12 are each independently a hydrogen atom or a methyl group, and R 13 is hydrogen, a methyl group, a butyl group, or a cyclohexyl group. More preferably, R 11 is a methyl group, and R 12 is hydrogen, and R 13 is a methyl group. The acrylic resin may contain only a single glutarimide unit, and R 11 , R 12 and R 13 Acrylic resins having glutarimide units may contain a plurality of glutarimide units having different groups. Examples of acrylic resins having glutarimide units are described in JP-A-2006-309033, JP-A-2006-317560, JP-A-2006-328334, JP-A-2006-337491, JP-A-2006-337492, JP-A-2006-337493, and JP-A-2006-337569, the disclosures of which are incorporated herein by reference. Note that the glutaric anhydride unit is represented by the formula (3) above, 13 The above description regarding the glutarimide unit applies, except that the nitrogen atom substituted with is an oxygen atom.

[0081] As for the maleic anhydride unit and the maleimide (N-substituted maleimide) unit, their structures are specified by their names, and therefore specific explanations are omitted.

[0082] The content of the repeating unit containing a ring structure in the acrylic resin is preferably 1 mol% to 50 mol%, more preferably 10 mol% to 40 mol%, and even more preferably 20 mol% to 30 mol%. If the content is too low, Tg may be less than 100°C, and the heat resistance, solvent resistance, and surface hardness of the resulting protective layer may be insufficient. If the content is too high, moldability and transparency may be insufficient.

[0083] The acrylic resin may contain repeating units other than the alkyl (meth)acrylate unit and the repeating unit containing a ring structure. Examples of such repeating units include repeating units derived from vinyl monomers copolymerizable with the monomers constituting the above units (other vinyl monomer units). Examples of other vinyl monomers include acrylic acid, methacrylic acid, crotonic acid, 2-(hydroxymethyl)acrylic acid, 2-(hydroxyethyl)acrylic acid, acrylonitrile, methacrylonitrile, ethacrylonitrile, allyl glycidyl ether, maleic anhydride, itaconic anhydride, N-methylmaleimide, N-ethylmaleimide, N-cyclohexylmaleimide, aminoethyl acrylate, propylaminoethyl acrylate, dimethylaminoethyl methacrylate, ethylaminopropyl methacrylate, cyclohexylaminoethyl methacrylate, N-vinyldiethylamine, N-acetylvinylamine, allylamine, methallylamine, N-methylallylamine, 2-isopropenyl-oxazoline, 2-vinyl-oxazoline, 2-acroyl-oxazoline, N-phenylmaleimide, phenylaminoethyl methacrylate, styrene, α-methylstyrene, p-glycidylstyrene, p-aminostyrene, and 2-styryl-oxazoline. These may be used alone or in combination. The type, number, combination, content ratio, etc. of the other vinyl monomer units may be appropriately set depending on the purpose.

[0084] The weight average molecular weight of the acrylic resin is preferably 1000 to 2000000, more preferably 5000 to 1000000, further preferably 10000 to 500000, particularly preferably 50000 to 500000, and most preferably 60000 to 150000. The weight average molecular weight can be determined, for example, using a gel permeation chromatograph (GPC system, manufactured by Tosoh Corporation) in terms of polystyrene. Tetrahydrofuran can be used as the solvent.

[0085] The acrylic resin can be polymerized by any suitable polymerization method using an appropriate combination of the above monomer units.

[0086] In the embodiment of the present invention, the acrylic resin may be used in combination with other resins. That is, the monomer components constituting the acrylic resin may be copolymerized with the monomer components constituting the other resins, and the copolymer may be used to form the protective layer described below; a blend of the acrylic resin and the other resin may be used to form the protective layer. Examples of the other resins include thermoplastic resins such as styrene resins, polyethylene, polypropylene, polyamide, polyphenylene sulfide, polyether ether ketone, polyester, polysulfone, polyphenylene oxide, polyacetal, polyimide, and polyetherimide. The type and amount of the resin used in combination may be appropriately set depending on the purpose and the properties desired for the resulting film. For example, a styrene resin (preferably, an acrylonitrile-styrene copolymer) may be used in combination as a retardation control agent.

[0087] When an acrylic resin is used in combination with another resin, the content of the acrylic resin in the blend of the acrylic resin and the other resin is preferably 50% by weight to 100% by weight, more preferably 60% by weight to 100% by weight, further preferably 70% by weight to 100% by weight, and particularly preferably 80% by weight to 100% by weight. If the content is less than 50% by weight, the high heat resistance and high transparency inherent to the acrylic resin may not be fully reflected.

[0088] B-3-2. Photocationically cured epoxy resin In one embodiment, the protective layer is composed of a photocationically cured product of an epoxy resin. By using such a protective layer, a polarizing plate and a polarizing plate with a retardation layer that have both excellent durability and excellent flexibility can be provided. As described above, since the protective layer is a photocationically cured product, the composition for forming the protective layer contains a photocationic polymerization initiator. The photocationic polymerization initiator is a photosensitive agent having a function of a photoacid generator, and a representative example is an ionic onium salt consisting of a cationic portion and an anionic portion. In this onium salt, the cationic portion absorbs light, and the anionic portion serves as a source of acid generation. The acid generated from this photocationic polymerization initiator causes ring-opening polymerization of the epoxy group. The protective layer, which is the obtained photocationically cured product, has a high glass transition temperature and can reduce the amount of iodine adsorption. Therefore, a polarizing plate that can have both excellent durability and excellent flexibility can be provided.

[0089] B-3-2-1.Epoxy resin Any suitable epoxy resin can be used as the epoxy resin. In the embodiment of the present invention, an epoxy resin having at least one selected from the group consisting of an aromatic skeleton and a hydrogenated aromatic skeleton can be used. Examples of the aromatic skeleton include a benzene ring, a naphthalene ring, and a fluorene ring. Only one type of epoxy resin may be used, or two or more types may be used in combination. An epoxy resin having a biphenyl skeleton as the aromatic skeleton is preferably used. By using an epoxy resin having a biphenyl skeleton, a polarizing plate having both excellent durability and excellent flexibility can be provided. Hereinafter, an epoxy resin having a biphenyl skeleton will be described in detail as a representative example.

[0090] In one embodiment, the epoxy resin having a biphenyl skeleton is an epoxy resin having the following structure: The epoxy resin having a biphenyl skeleton may be used alone or in combination of two or more kinds. [ka] (In the formula, R 14 ~R 21 each independently represents a hydrogen atom, a linear or branched, substituted or unsubstituted hydrocarbon group having 1 to 12 carbon atoms, or a halogen element).

[0091] R 14 ~R 21 each independently represents a hydrogen atom, a linear or branched, substituted or unsubstituted hydrocarbon group having 1 to 12 carbon atoms, or a halogen element. Examples of linear or branched, substituted or unsubstituted hydrocarbon groups having 1 to 12 carbon atoms include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, a neopentyl group, a tert-pentyl group, a cyclopentyl group, an n-hexyl group, an isohexyl group, a cyclohexyl group, an n-heptyl group, a cycloheptyl group, a methylcyclohexyl group, an n-octyl group, a cyclooctyl group, an n-nonyl group, a 3,3,5-trimethylcyclohexyl group, an n-decyl group, a cyclodecyl group, an n-undecyl group, an n-dodecyl group, a cyclododecyl group, a phenyl group, a benzyl group, a methylbenzyl group, a dimethylbenzyl group, a trimethylbenzyl group, a naphthylmethyl group, a phenethyl group, and a 2-phenylisopropyl group. The linear or branched, substituted or unsubstituted hydrocarbon group having 1 to 12 carbon atoms preferably includes an alkyl group having 1 to 4 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, etc. The halogen element preferably includes fluorine and bromine.

[0092] In one embodiment, the epoxy resin having a biphenyl skeleton is an epoxy resin represented by the following formula: [ka] (In the formula, R 14 ~R 21 is as above, and n represents an integer of 0 to 6).

[0093] In one embodiment, the epoxy resin having a biphenyl skeleton is an epoxy resin having only a biphenyl skeleton. By using an epoxy resin having only a biphenyl skeleton, the durability of the obtained protective layer can be further improved.

[0094] In one embodiment, the epoxy resin having a biphenyl skeleton may contain a chemical structure other than the biphenyl skeleton. Examples of the chemical structure other than the biphenyl skeleton include a bisphenol skeleton, an alicyclic structure, and an aromatic ring structure. In this embodiment, the proportion (molar ratio) of the chemical structure other than the biphenyl skeleton is preferably smaller than that of the biphenyl skeleton.

[0095] The epoxy resin having a biphenyl skeleton may be a commercially available product, such as those manufactured by Mitsubishi Chemical Corporation under the trade names jER YX4000, jER YX4000H, jER YL6121, jER YL664, jER YL6677, jER YL6810, and jER YL7399.

[0096] The epoxy resin having a biphenyl skeleton preferably has a glass transition temperature (Tg) of 90° C. or higher. As a result, the Tg of the protective layer is 90° C. or higher. If the Tg of the epoxy resin having a biphenyl skeleton is 90° C. or higher, the polarizing plate including the obtained protective layer is likely to have excellent durability. The Tg of the epoxy resin having a biphenyl skeleton is preferably 100° C. or higher, more preferably 110° C. or higher, even more preferably 120° C. or higher, and particularly preferably 125° C. or higher. On the other hand, the Tg of the epoxy resin having a biphenyl skeleton is preferably 300° C. or lower, more preferably 250° C. or lower, even more preferably 200° C. or lower, and particularly preferably 160° C. or lower. If the Tg of the epoxy resin having a biphenyl skeleton is within such a range, it may have excellent moldability.

[0097] The epoxy equivalent of the epoxy resin having a biphenyl skeleton is preferably 100 g / equivalent or more, more preferably 150 g / equivalent or more, and even more preferably 200 g / equivalent or more. The epoxy equivalent of the epoxy resin having a biphenyl skeleton is preferably 3000 g / equivalent or less, more preferably 2500 g / equivalent or less, and even more preferably 2000 g / equivalent or less. By the epoxy equivalent of the epoxy resin having a biphenyl skeleton being within the above range, a more stable protective layer (a protective layer with less residual monomer and sufficiently cured) can be obtained. In this specification, the term "epoxy equivalent" refers to the "mass of an epoxy resin containing one equivalent of epoxy group" and can be measured in accordance with JIS K7236.

[0098] In an embodiment of the present invention, an epoxy resin having at least one selected from the group consisting of an aromatic skeleton and a hydrogenated aromatic skeleton may be used in combination with another resin. That is, a blend of an epoxy resin having at least one selected from the group consisting of an aromatic skeleton and a hydrogenated aromatic skeleton and another resin may be used to form a protective layer. Examples of the other resin include thermoplastic resins such as styrene-based resins, polyethylene, polypropylene, polyamide, polyphenylene sulfide, polyether ether ketone, polyester, polysulfone, polyphenylene oxide, polyacetal, polyimide, and polyetherimide, and curable resins such as acrylic resins and oxetane resins. Preferably, acrylic resins and oxetane resins are used. The type and amount of the resin used in combination can be appropriately set depending on the purpose and the properties desired for the resulting film. For example, a styrene-based resin can be used in combination as a retardation control agent.

[0099] Any suitable acrylic resin can be used as the acrylic resin. For example, the (meth)acrylic compound includes, for example, a (meth)acrylic compound having one (meth)acryloyl group in the molecule (hereinafter also referred to as a "monofunctional (meth)acrylic compound") and a (meth)acrylic compound having two or more (meth)acryloyl groups in the molecule (hereinafter also referred to as a "polyfunctional (meth)acrylic compound"). These (meth)acrylic compounds may be used alone or in combination of two or more. These acrylic resins are described, for example, in JP 2019-168500 A. The entire disclosure of this publication is incorporated herein by reference.

[0100] As the oxetane resin, any suitable compound having one or more oxetanyl groups in the molecule can be used. Examples of the oxetane compounds include oxetane compounds having one oxetanyl group in the molecule, such as 3-ethyl-3-hydroxymethyloxetane, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, 3-ethyl-3-(phenoxymethyl)oxetane, 3-ethyl-3-(cyclohexyloxymethyl)oxetane, 3-ethyl-3-(oxiranylmethoxy)oxetane, and (3-ethyloxetan-3-yl)methyl (meth)acrylate; and oxetane compounds having two or more oxetanyl groups in the molecule, such as 3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane, 1,4-bis[(3-ethyl-3-oxetanyl)methoxymethyl]benzene, and 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl. These oxetane resins may be used alone or in combination of two or more.

[0101] As the oxetane resin, preferably used are 3-ethyl-3-hydroxymethyloxetane, 1,4-bis[(3-ethyl-3-oxetanyl)methoxymethyl]benzene, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, 3-ethyl-3-(oxiranylmethoxy)oxetane, (3-ethyloxetan-3-yl)methyl (meth)acrylate, 3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane, etc. These oxetane resins are easily available and can have excellent dilution properties (low viscosity) and compatibility.

[0102] In one embodiment, from the viewpoint of compatibility and adhesiveness, an oxetane resin having a molecular weight of 500 or less and being liquid at room temperature (25° C.) is used. In one embodiment, an oxetane compound containing two or more oxetanyl groups in the molecule, an oxetane compound containing one oxetanyl group and one (meth)acryloyl group or one epoxy group in the molecule is preferably used, and more preferably 3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane, 3-ethyl-3-(oxiranylmethoxy)oxetane, or (3-ethyloxetan-3-yl)methyl (meth)acrylate is used. By using these oxetane resins, the curability and durability of the protective layer can be improved.

[0103] As the oxetane resin, a commercially available product may be used. Specifically, ARON OXT-101, ARON OXT-121, ARON OXT-212, and ARON OXT-221 (all manufactured by Toagosei Co., Ltd.) may be used. Preferably, ARON OXT-101 and ARON OXT-221 may be used.

[0104] When an epoxy resin having at least one selected from the group consisting of an aromatic skeleton and a hydrogenated aromatic skeleton is used in combination with another resin, the content of the epoxy resin having at least one selected from the group consisting of an aromatic skeleton and a hydrogenated aromatic skeleton in the blend of the epoxy resin having at least one selected from the group consisting of an aromatic skeleton and a hydrogenated aromatic skeleton with the other resin is preferably 50% by weight to 100% by weight, more preferably 60% by weight to 100% by weight, even more preferably 70% by weight to 100% by weight, and particularly preferably 80% by weight to 100% by weight. If the content is less than 50% by weight, there is a risk that the heat resistance of the protective layer and sufficient adhesion to the polarizer cannot be obtained.

[0105] When an epoxy resin having a biphenyl skeleton and an oxetane resin are used in combination, the content of the oxetane resin is preferably 1 to 50 parts by weight, more preferably 5 to 45 parts by weight, and even more preferably 10 to 40 parts by weight, relative to 100 parts by weight of the total amount of the epoxy resin having a biphenyl skeleton and the oxetane resin. By setting the content within the above range, the curability is improved, and the adhesion between the protective layer and the polarizer can also be improved.

[0106] B-3-2-2. Photocationic polymerization initiator The photocationic polymerization initiator is a photosensitive agent having the function of a photoacid generator, and a representative example is an ionic onium salt consisting of a cationic portion and an anionic portion. In this onium salt, the cationic portion absorbs light, and the anionic portion serves as a source of acid generation. The acid generated from this photocationic polymerization initiator causes ring-opening polymerization of the epoxy group. As the photocationic polymerization initiator, any suitable compound that can cure an epoxy resin having at least one selected from the group consisting of an aromatic skeleton and a hydrogenated aromatic skeleton by irradiation with light such as ultraviolet light can be used. Only one type of photocationic polymerization initiator may be used, or two or more types may be used in combination.

[0107] Examples of the photocationic polymerization initiator include triphenylsulfonium hexafluoroantimonate, triphenylsulfonium hexafluorophosphate, p-(phenylthio)phenyl diphenylsulfonium hexafluoroantimonate, p-(phenylthio)phenyl diphenylsulfonium hexafluorophosphate, 4-chlorophenyl diphenylsulfonium hexafluorophosphate, 4-chlorophenyl diphenylsulfonium hexafluoroantimonate, bis[4-(diphenylsulfonio)phenyl]sulfide bishexafluorophosphate, bis[4-(diphenylsulfonio)phenyl]sulfide bishexafluoroantimonate, (2,4-cyclopentadiene-1-yl)[(1-methylethyl)benzene]-Fe-hexafluorophosphate, and diphenyliodonium hexafluoroantimonate. Preferably, a triphenylsulfonium salt-based hexafluoroantimonate type photocationic polymerization initiator or a diphenyliodonium salt-based hexafluoroantimonate type photocationic polymerization initiator is used.

[0108] The photocationic polymerization initiator may be a commercially available product, such as triphenylsulfonium salt-based hexafluoroantimonate type SP-170 (manufactured by ADEKA Corporation), CPI-101A (manufactured by San-Apro Corporation), WPAG-1056 (manufactured by Wako Pure Chemical Industries, Ltd.), diphenyliodonium salt-based hexafluoroantimonate type WPI-116 (manufactured by Wako Pure Chemical Industries, Ltd.), etc.

[0109] The content of the cationic photopolymerization initiator is preferably 0.1 to 3 parts by weight, more preferably 0.25 to 2 parts by weight, based on 100 parts by weight of the epoxy resin having at least one selected from the group consisting of an aromatic skeleton and a hydrogenated aromatic skeleton. If the content of the cationic photopolymerization initiator is less than 0.1 part by weight, the epoxy resin may not be sufficiently cured even when irradiated with light (ultraviolet rays).

[0110] B-3-3.Solidified coating of epoxy resin in organic solvent solution In one embodiment, the protective layer is formed by solidifying a coating film of an epoxy resin in an organic solvent.

[0111] B-3-3-1.Epoxy resin In this embodiment, the epoxy resin preferably has a glass transition temperature (Tg) of 90° C. or higher. As a result, the protective layer has a Tg of 90° C. or higher. If the epoxy resin has a Tg of 90° C. or higher, a polarizing plate including a protective layer obtained from such a resin is likely to have excellent durability. The epoxy resin preferably has a Tg of 100° C. or higher, more preferably 110° C. or higher, even more preferably 120° C. or higher, and particularly preferably 125° C. or higher. On the other hand, the epoxy resin preferably has a Tg of 300° C. or lower, more preferably 250° C. or lower, even more preferably 200° C. or lower, and particularly preferably 160° C. or lower. If the epoxy resin has a Tg in this range, it can have excellent moldability.

[0112] As the epoxy resin, any suitable epoxy resin may be adopted as long as it has the above-mentioned Tg. The epoxy resin typically refers to a resin having an epoxy group in its molecular structure. As the epoxy resin, an epoxy resin having an aromatic ring in its molecular structure is preferably used. By using an epoxy resin having an aromatic ring, an epoxy resin having a higher Tg can be obtained. Examples of the aromatic ring in the epoxy resin having an aromatic ring in its molecular structure include a benzene ring, a naphthalene ring, and a fluorene ring. Only one type of epoxy resin may be used, or two or more types may be used in combination. When two or more types of epoxy resins are used, an epoxy resin having an aromatic ring and an epoxy resin not having an aromatic ring may be used in combination.

[0113] Specific examples of epoxy resins having an aromatic ring in the molecular structure include bisphenol A diglycidyl ether type epoxy resins, bisphenol F diglycidyl ether type epoxy resins, bisphenol S diglycidyl ether type epoxy resins, resorcinol diglycidyl ether type epoxy resins, hydroquinone diglycidyl ether type epoxy resins, terephthalic acid diglycidyl ester type epoxy resins, bisphenoxyethanol fluorene diglycidyl ether type epoxy resins, bisphenol fluorene diglycidyl ether type epoxy resins, and biscresol fluorene diglycidyl ether type epoxy resins. Examples of epoxy resins include epoxy resins having two epoxy groups such as phenol-type epoxy resins; epoxy resins having three epoxy groups such as novolac-type epoxy resins, N,N,O-triglycidyl-P- or -m-aminophenol-type epoxy resins, N,N,O-triglycidyl-4-amino-m- or -5-amino-o-cresol-type epoxy resins, and 1,1,1-(triglycidyloxyphenyl)methane-type epoxy resins; and epoxy resins having four epoxy groups such as glycidylamine-type epoxy resins (e.g., diaminodiphenylmethane type, diaminodiphenylsulfone type, and metaxylenediamine type). In addition, glycidyl ester-type epoxy resins such as hexahydrophthalic anhydride-type epoxy resins, tetrahydrophthalic anhydride-type epoxy resins, dimer acid-type epoxy resins, and p-oxybenzoic acid-type epoxy resins may also be used.

[0114] The weight average molecular weight of the epoxy resin is preferably 1000 to 2000000, more preferably 5000 to 1000000, further preferably 10000 to 500000, particularly preferably 50000 to 500000, and most preferably 60000 to 150000. The weight average molecular weight can be determined, for example, using a gel permeation chromatograph (GPC system, manufactured by Tosoh Corporation) in terms of polystyrene. Tetrahydrofuran can be used as the solvent.

[0115] The epoxy equivalent of the epoxy resin is preferably 1000 g / equivalent or more, more preferably 3000 g / equivalent or more, and even more preferably 5000 g / equivalent or more. The epoxy equivalent of the epoxy resin is preferably 30000 g / equivalent or less, more preferably 25000 g / equivalent or less, and even more preferably 20000 g / equivalent or less. By setting the epoxy equivalent within the above range, a more stable protective layer can be obtained. In this specification, the term "epoxy equivalent" refers to the "mass of an epoxy resin containing one equivalent of epoxy groups" and can be measured in accordance with JIS K7236.

[0116] In the embodiment of the present invention, the epoxy resin may be used in combination with other resins. That is, a blend of the epoxy resin and other resins may be used to form the protective layer. Examples of the other resins include thermoplastic resins such as styrene-based resins, polyethylene, polypropylene, polyamide, polyphenylene sulfide, polyether ether ketone, polyester, polysulfone, polyphenylene oxide, polyacetal, polyimide, and polyetherimide. The type and amount of the resin used in combination may be appropriately set depending on the purpose and the desired properties of the resulting film. For example, the styrene-based resin may be used in combination as a retardation control agent.

[0117] When an epoxy resin is used in combination with another resin, the content of the epoxy resin in the blend of the epoxy resin and the other resin is preferably 50% by weight to 100% by weight, more preferably 60% by weight to 100% by weight, further preferably 70% by weight to 100% by weight, and particularly preferably 80% by weight to 100% by weight. If the content is less than 50% by weight, the heat resistance of the protective layer and sufficient adhesion to the polarizer may not be obtained.

[0118] B-3-4. Composition and characteristics of protective layer In one embodiment, the protective layer is composed of at least one selected from the group consisting of a solidified coating film of an organic solvent solution of a thermoplastic acrylic resin, a photocationically cured product of an epoxy resin, and a solidified coating film of an organic solvent solution of an epoxy resin, as described above. Such a protective layer can be made significantly thinner than an extrusion-molded film. The thickness of the protective layer is 10 μm or less, as described above. Although not theoretically clear, such a protective layer has the advantages of being smaller in shrinkage during film molding than cured products of other thermosetting resins or active energy ray-curable resins (e.g., ultraviolet-curable resins), and being free of residual monomers, etc., suppressing deterioration of the film itself, and suppressing adverse effects on the polarizing plate (polarizer) caused by residual monomers, etc. Furthermore, it has the advantage of being excellent in humidification durability because it has smaller hygroscopicity and moisture permeability than solidified products of aqueous coating films such as aqueous solutions or aqueous dispersions. As a result, a polarizing plate with excellent durability that can maintain optical properties even under a heated and humidified environment can be realized.

[0119] The Tg of the protective layer is as described for the acrylic resin and the epoxy resin.

[0120] The protective layer is preferably substantially optically isotropic. In this specification, "substantially optically isotropic" means that the in-plane retardation Re(550) is 0 nm to 10 nm, and the thickness direction retardation Rth(550) is -20 nm to +10 nm. The in-plane retardation Re(550) is more preferably 0 nm to 5 nm, further preferably 0 nm to 3 nm, and particularly preferably 0 nm to 2 nm. The thickness direction retardation Rth(550) is more preferably -5 nm to +5 nm, further preferably -3 nm to +3 nm, and particularly preferably -2 nm to +2 nm. If the Re(550) and Rth(550) of the protective layer are in such ranges, it is possible to prevent adverse effects on the display characteristics when a polarizing plate including the protective layer is applied to an image display device. Note that Re(550) is the in-plane retardation of the film measured with light having a wavelength of 550 nm at 23°C. Re(550) is calculated by the formula: Re(550)=(nx-ny)×d. Rth(550) is the retardation in the thickness direction of the film measured with light having a wavelength of 550 nm at 23° C. Rth(550) is calculated by the formula: Rth(550)=(nx-nz)×d. Here, nx is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), ny is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), nz is the refractive index in the thickness direction, and d is the thickness of the film (nm).

[0121] The higher the light transmittance at 380 nm when the protective layer is 3 μm thick, the more preferable. Specifically, the light transmittance is preferably 85% or more, more preferably 88% or more, and even more preferably 90% or more. If the light transmittance is within this range, the desired transparency can be ensured. The light transmittance can be measured, for example, by a method conforming to ASTM-D-1003.

[0122] The lower the haze of the protective layer, the better. Specifically, the haze is preferably 5% or less, more preferably 3% or less, even more preferably 1.5% or less, and particularly preferably 1% or less. When the haze is 5% or less, the film can have a good sense of clarity. Furthermore, even when used as a polarizing plate on the viewing side of an image display device, the displayed content can be easily viewed.

[0123] The YI at a thickness of 3 μm of the protective layer is preferably 1.27 or less, more preferably 1.25 or less, even more preferably 1.23 or less, and particularly preferably 1.20 or less. If the YI exceeds 1.3, the optical transparency may be insufficient. The YI can be calculated by the following formula from the tristimulus values ​​(X, Y, Z) of the color obtained by measurement using a high-speed integrating sphere type spectral transmittance measuring device (product name DOT-3C: manufactured by Murakami Color Research Laboratory). YI = [(1.28X-1.06Z) / Y] x 100

[0124] The b value (a measure of hue according to the Hunter color system) of the protective layer at a thickness of 3 μm is preferably less than 1.5, more preferably 1.0 or less. If the b value is 1.5 or more, an undesired color tone may appear. The b value can be obtained, for example, by cutting a sample of the film constituting the protective layer into a 3 cm square, measuring the hue using a high-speed integrating sphere type spectral transmittance measuring device (product name DOT-3C: manufactured by Murakami Color Research Laboratory), and evaluating the hue according to the Hunter color system.

[0125] The protective layer (for example, a solidified product of a coating film or a photocationically cured product) may contain any suitable additive depending on the purpose. Specific examples of additives include ultraviolet absorbers; leveling agents; antioxidants such as hindered phenols, phosphorus, and sulfur; stabilizers such as light stabilizers, weather stabilizers, and heat stabilizers; reinforcing materials such as glass fibers and carbon fibers; near-infrared absorbers; flame retardants such as tris(dibromopropyl)phosphate, triallyl phosphate, and antimony oxide; antistatic agents such as anionic, cationic, and nonionic surfactants; colorants such as inorganic pigments, organic pigments, and dyes; organic or inorganic fillers; resin modifiers; organic and inorganic fillers; plasticizers; lubricants; antistatic agents; and flame retardants. The additives may be added during polymerization of the acrylic resin, or may be added to the solution during film formation. The type, number, combination, and amount of additives may be appropriately set depending on the purpose.

[0126] An easy-adhesion layer may be formed on the polarizer side of the protective layer. The easy-adhesion layer contains, for example, a water-based polyurethane and an oxazoline-based crosslinking agent. By forming such an easy-adhesion layer, the adhesion between the protective layer and the polarizer can be increased. In addition, a hard coat layer may be formed on the protective layer. In addition, when a hard coat layer is formed, the hard coat layer may be formed so that the total thickness of the protective layer (for example, the solidified product of the coating film) and the hard coat layer is 10 μm or less. The hard coat layer may be formed when the protective layer is used as a protective layer on the viewing side of the viewing-side polarizing plate. When both the easy-adhesion layer and the hard coat layer are formed, they may be typically formed on different sides of the protective layer.

[0127] C. First retardation layer As described above, the first retardation layer 20 is an alignment-solidified layer of a liquid crystal compound. By using a liquid crystal compound, the difference between nx and ny of the obtained retardation layer can be significantly increased compared to non-liquid crystal materials, so that the thickness of the retardation layer for obtaining a desired in-plane retardation can be significantly reduced. As a result, it is possible to realize a further reduction in thickness and weight of the retardation layer-attached polarizing plate. In this specification, the "alignment-solidified layer" refers to a layer in which the liquid crystal compound is aligned in a predetermined direction within the layer and the alignment state is fixed. Note that the "alignment-solidified layer" is a concept that includes an alignment-solidified layer obtained by hardening a liquid crystal monomer as described later. In this embodiment, typically, rod-shaped liquid crystal compounds are aligned in the slow axis direction of the first retardation layer (homogeneous alignment).

[0128] Examples of liquid crystal compounds include liquid crystal compounds whose liquid crystal phase is a nematic phase (nematic liquid crystals). Examples of such liquid crystal compounds include liquid crystal polymers and liquid crystal monomers. The mechanism by which liquid crystallinity of liquid crystal compounds is expressed may be either lyotropic or thermotropic. The liquid crystal polymers and liquid crystal monomers may be used alone or in combination.

[0129] When the liquid crystal compound is a liquid crystal monomer, the liquid crystal monomer is preferably a polymerizable monomer and a crosslinkable monomer. This is because the alignment state of the liquid crystal monomer can be fixed by polymerizing or crosslinking (i.e., curing) the liquid crystal monomer. After the liquid crystal monomer is aligned, for example, the liquid crystal monomers can be polymerized or crosslinked with each other, thereby fixing the alignment state. Here, a polymer is formed by polymerization, and a three-dimensional network structure is formed by crosslinking, but these are non-liquid crystals. Therefore, the formed first retardation layer does not undergo transition to a liquid crystal phase, a glass phase, or a crystalline phase due to temperature changes specific to liquid crystal compounds, for example. As a result, the first retardation layer becomes a retardation layer that is not affected by temperature changes and has extremely excellent stability.

[0130] The temperature range in which the liquid crystal monomer exhibits liquid crystallinity varies depending on the type of the liquid crystal monomer. Specifically, the temperature range is preferably 40°C to 120°C, more preferably 50°C to 100°C, and further preferably 60°C to 90°C.

[0131] Any suitable liquid crystal monomer can be used as the liquid crystal monomer. For example, the polymerizable mesogen compounds described in JP-A-2002-533742 (WO00 / 37585), EP358208 (US5211877), EP66137 (US4388453), WO93 / 22397, EP0261712, DE19504224, DE4408171, and GB2280445 can be used. Specific examples of such polymerizable mesogen compounds include BASF's product name LC242, Merck's product name E7, and Wacker-Chem's product name LC-Sillicon-CC3767. For example, nematic liquid crystal monomers are preferred as the liquid crystal monomer.

[0132] The alignment and solidification layer of the liquid crystal compound can be formed by performing an alignment treatment on the surface of a predetermined substrate, applying a coating liquid containing a liquid crystal compound to the surface to align the liquid crystal compound in a direction corresponding to the alignment treatment, and fixing the alignment state. In one embodiment, the substrate is any appropriate resin film, and the alignment and solidification layer formed on the substrate can be transferred to the surface of the polarizing plate 10. In another embodiment, the substrate can be the second protective layer 13. In this case, the transfer step is omitted, and lamination can be performed by roll-to-roll immediately after the formation of the alignment and solidification layer (first retardation layer), further improving productivity.

[0133] As the above-mentioned alignment treatment, any suitable alignment treatment can be adopted. Specifically, mechanical alignment treatment, physical alignment treatment, and chemical alignment treatment can be mentioned. Specific examples of mechanical alignment treatment include rubbing treatment and stretching treatment. Specific examples of physical alignment treatment include magnetic field alignment treatment and electric field alignment treatment. Specific examples of chemical alignment treatment include oblique deposition method and photoalignment treatment. As the treatment conditions of various alignment treatments, any suitable conditions can be adopted according to the purpose.

[0134] The alignment of the liquid crystal compound is performed by treating the liquid crystal compound at a temperature at which the liquid crystal compound exhibits a liquid crystal phase according to the type of liquid crystal compound. By performing such temperature treatment, the liquid crystal compound takes on a liquid crystal state and is aligned according to the alignment treatment direction of the substrate surface.

[0135] In one embodiment, the alignment state is fixed by cooling the liquid crystal compound aligned as described above. When the liquid crystal compound is a polymerizable monomer or a crosslinkable monomer, the alignment state is fixed by subjecting the liquid crystal compound aligned as described above to a polymerization treatment or a crosslinking treatment.

[0136] Specific examples of the liquid crystal compound and details of the method for forming the alignment solidified layer are described in JP-A-2006-163343, the disclosure of which is incorporated herein by reference.

[0137] Another example of the alignment solidified layer is a form in which the discotic liquid crystal compound is aligned in any one of vertical alignment, hybrid alignment, and tilt alignment. The discotic liquid crystal compound is typically aligned such that the disc surface of the discotic liquid crystal compound is substantially perpendicular to the film surface of the first retardation layer. The discotic liquid crystal compound being substantially perpendicular means that the average angle between the film surface and the disc surface of the discotic liquid crystal compound is preferably 70° to 90°, more preferably 80° to 90°, and even more preferably 85° to 90°. The discotic liquid crystal compound generally refers to a liquid crystal compound having a discotic molecular structure in which a cyclic mother nucleus such as benzene, 1,3,5-triazine, or calixarene is arranged at the center of the molecule, and linear alkyl groups, alkoxy groups, substituted benzoyloxy groups, or the like are radially substituted as side chains. Representative examples of discotic liquid crystals include benzene derivatives, triphenylene derivatives, truxene derivatives, and phthalocyanine derivatives described in the research report by C. Destrade et al., Mol. Cryst. Liq. Cryst., Vol. 71, p. 111 (1981); cyclohexane derivatives described in the research report by B. Kohne et al., Angew. Chem. Vol. 96, p. 70 (1984); and azacrown and phenylacetylene macrocycles described in the research report by JM Lehn et al., J. Chem. Soc. Chem. Commun., p. 1794 (1985) and the research report by J. Zhang et al., J. Am. Chem. Soc., Vol. 116, p. 2655 (1994). Further specific examples of discotic liquid crystal compounds include those described in JP-A-2006-133652, JP-A-2007-108732, and JP-A-2010-244038, the disclosures of which are incorporated herein by reference.

[0138] In one embodiment, as shown in FIGS. 1 and 2, the first retardation layer 20 is a single layer of an alignment and solidification layer of a liquid crystal compound. When the first retardation layer 20 is composed of a single layer of an alignment and solidification layer of a liquid crystal compound, its thickness is preferably 0.5 μm to 7 μm, more preferably 1 μm to 5 μm. By using a liquid crystal compound, an in-plane retardation equivalent to that of a resin film can be realized with a thickness much thinner than that of the resin film.

[0139] Typically, the first retardation layer exhibits a refractive index characteristic of nx > ny = nz. The first retardation layer is typically provided to impart an antireflection characteristic to a polarizing plate, and when the first retardation layer is a single layer of an alignment and solidification layer, it can function as a λ / 4 plate. In this case, the in-plane retardation Re(550) of the first retardation layer is preferably 100 nm to 190 nm, more preferably 110 nm to 170 nm, and even more preferably 130 nm to 160 nm. Here, "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range that does not impair the effects of the present invention, ny > nz or ny < nz may occur.

[0140] The Nz coefficient of the first retardation layer is preferably 0.9 to 1.5, more preferably 0.9 to 1.3. By satisfying such a relationship, when the polarizing plate with a retardation layer is used in an image display device, a very excellent reflected hue can be achieved.

[0141] The first retardation layer may exhibit an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light, a positive wavelength dispersion characteristic in which the retardation value decreases according to the wavelength of the measurement light, or a flat wavelength dispersion characteristic in which the retardation value hardly changes depending on the wavelength of the measurement light. In one embodiment, the first retardation layer exhibits an inverse dispersion wavelength characteristic. In this case, Re(450) / Re(550) of the retardation layer is preferably 0.8 or more and less than 1, more preferably 0.8 or more and 0.95 or less. With such a configuration, a very excellent antireflection characteristic can be realized.

[0142] The angle θ between the slow axis of the first retardation layer 20 and the absorption axis of the polarizer 11 is preferably 40° to 50°, more preferably 42° to 48°, and further preferably about 45°. If the angle θ is in such a range, by using a λ / 4 plate as the first retardation layer as described above, a retardation layer-attached polarizing plate having very excellent circular polarization properties (resulting in very excellent antireflection properties) can be obtained.

[0143] In another embodiment, the first retardation layer 20 may have a laminated structure of a first alignment solidified layer 21 and a second alignment solidified layer 22 as shown in FIG. 3. In this case, either the first alignment solidified layer 21 or the second alignment solidified layer 22 may function as a λ / 4 plate, and the other may function as a λ / 2 plate. Therefore, the thicknesses of the first alignment solidified layer 21 and the second alignment solidified layer 22 may be adjusted so as to obtain a desired in-plane retardation of a λ / 4 plate or a λ / 2 plate. For example, when the first alignment solidified layer 21 functions as a λ / 2 plate and the second alignment solidified layer 22 functions as a λ / 4 plate, the thickness of the first alignment solidified layer 21 is, for example, 2.0 μm to 3.0 μm, and the thickness of the second alignment solidified layer 22 is, for example, 1.0 μm to 2.0 μm. In this case, the in-plane retardation Re(550) of the first alignment solidified layer is preferably 200 nm to 300 nm, more preferably 230 nm to 290 nm, and further preferably 250 nm to 280 nm. The in-plane retardation Re(550) of the second alignment solidified layer is as described above for the single-layer alignment solidified layer. The angle between the slow axis of the first alignment solidified layer and the absorption axis of the polarizer is preferably 10° to 20°, more preferably 12° to 18°, and further preferably about 15°. The angle between the slow axis of the second alignment solidified layer and the absorption axis of the polarizer is preferably 70° to 80°, more preferably 72° to 78°, and further preferably about 75°. With such a configuration, it is possible to obtain characteristics close to ideal reverse wavelength dispersion characteristics, and as a result, it is possible to realize very excellent antireflection characteristics. The liquid crystal compounds constituting the first alignment solidified layer and the second alignment solidified layer, the methods for forming the first alignment solidified layer and the second alignment solidified layer, the optical characteristics, etc. are as described above for the single alignment solidified layer.

[0144] D. Second retardation layer As described above, the second retardation layer may be a so-called positive C plate whose refractive index characteristics show the relationship nz>nx=ny. By using a positive C plate as the second retardation layer, it is possible to effectively prevent reflection in an oblique direction, and the anti-reflection function can be made to have a wide viewing angle. In this case, the thickness direction retardation Rth(550) of the second retardation layer is preferably -50 nm to -300 nm, more preferably -70 nm to -250 nm, further preferably -90 nm to -200 nm, and particularly preferably -100 nm to -180 nm. Here, "nx=ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. That is, the in-plane retardation Re(550) of the second retardation layer may be less than 10 nm.

[0145] The second retardation layer having a refractive index characteristic of nz>nx=ny may be formed of any appropriate material. The second retardation layer is preferably made of a film containing a liquid crystal material fixed in a homeotropic alignment. The liquid crystal material (liquid crystal compound) that can be homeotropically aligned may be a liquid crystal monomer or a liquid crystal polymer. Specific examples of the liquid crystal compound and the method of forming the retardation layer include the liquid crystal compound and the method of forming the retardation layer described in

[0020] to

[0028] of JP-A-2002-333642. In this case, the thickness of the second retardation layer is preferably 0.5 μm to 10 μm, more preferably 0.5 μm to 8 μm, and even more preferably 0.5 μm to 5 μm.

[0146] E. Conductive layer or isotropic substrate with conductive layer The conductive layer can be formed by forming a metal oxide film on any suitable substrate by any suitable film forming method (e.g., vacuum deposition, sputtering, CVD, ion plating, spraying, etc.). Examples of metal oxides include indium oxide, tin oxide, zinc oxide, indium-tin composite oxide, tin-antimony composite oxide, zinc-aluminum composite oxide, and indium-zinc composite oxide. Among these, indium-tin composite oxide (ITO) is preferred.

[0147] When the conductive layer contains a metal oxide, the thickness of the conductive layer is preferably 50 nm or less, more preferably 35 nm or less, and is preferably 10 nm or more.

[0148] The conductive layer may be transferred from the substrate to the first retardation layer (or the second retardation layer, if present) and used alone as a constituent layer of the retardation layer-attached polarizing plate, or may be laminated with the substrate (substrate with conductive layer) to the first retardation layer (or the second retardation layer, if present). Preferably, the substrate is optically isotropic, and therefore the conductive layer can be used in the retardation layer-attached polarizing plate as an isotropic substrate with conductive layer.

[0149] Any suitable isotropic substrate may be used as the optically isotropic substrate (isotropic substrate). Examples of materials constituting the isotropic substrate include materials having a resin without a conjugated system, such as norbornene resins and olefin resins, as the main skeleton, and materials having a ring structure, such as a lactone ring or a glutarimide ring, in the main chain of an acrylic resin. By using such materials, when the isotropic substrate is formed, the appearance of retardation due to the orientation of molecular chains can be suppressed to a small value. The thickness of the isotropic substrate is preferably 50 μm or less, more preferably 35 μm or less. The thickness of the isotropic substrate is, for example, 20 μm or more.

[0150] The conductive layer and / or the conductive layer of the isotropic substrate with a conductive layer may be patterned as necessary. By patterning, a conductive portion and an insulating portion may be formed. As a result, an electrode may be formed. The electrode may function as a touch sensor electrode that senses contact with the touch panel. Any appropriate method may be adopted as the patterning method. Specific examples of the patterning method include a wet etching method and a screen printing method.

[0151] F. Image display device The retardation layer-attached polarizing plate described in the above items A to E can be applied to an image display device. Therefore, the present invention includes an image display device using such a retardation layer-attached polarizing plate. Representative examples of image display devices include liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices and inorganic EL display devices). An image display device according to an embodiment of the present invention includes the retardation layer-attached polarizing plate described in the above items A to E on the viewing side. The retardation layer-attached polarizing plate is laminated so that the retardation layer is on the image display cell (e.g., liquid crystal cell, organic EL cell, inorganic EL cell) side (so that the polarizer is on the viewing side). In one embodiment, the image display device has a curved shape (substantially a curved display screen) and / or can be bent or folded. In such an image display device, the effect of the retardation layer-attached polarizing plate of the present invention becomes remarkable. EXAMPLES

[0152] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The methods for measuring each property are as follows. In the examples and comparative examples, "parts" and "%" are by weight unless otherwise specified.

[0153] [Example 1] 1. Preparation of Polarizer The thermoplastic resin substrate was a long, amorphous, isophthalic copolymerized polyethylene terephthalate film (thickness: 100 μm) with a water absorption rate of 0.75% and a Tg of approximately 75°C. One side of the resin substrate was subjected to corona treatment (treatment conditions: 55 W min / m 2 ) was applied. A PVA aqueous solution (coating solution) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin prepared by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name "GOHSEFFIMER Z410") in a ratio of 9:1. The above PVA aqueous solution was applied to the corona-treated surface of a resin substrate and dried at 60° C. to form a PVA-based resin layer having a thickness of 13.5 μm, thereby producing a laminate. The obtained laminate was uniaxially stretched at its free end to 2.4 times its original size in the machine direction (longitudinal direction) between rolls with different peripheral speeds in an oven at 130° C. (auxiliary air stretching treatment). Next, the laminate was immersed in an insolubilizing bath (a boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilizing treatment). Next, the film was immersed in a dye bath (iodine aqueous solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the single transmittance (Ts) of the final polarizer would be 40.5% (dyeing process). Next, the piece was immersed in a crosslinking bath (a boric acid aqueous solution obtained by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment). Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration 4.0 wt %, potassium iodide 5.0 wt %) at a liquid temperature of 62°C and uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds so that the total stretch ratio was 3.0 times (underwater stretching treatment: the stretch ratio in the underwater stretching treatment was 1.25 times). Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution obtained by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment). Thereafter, while drying in an oven maintained at 90°C, it was brought into contact with a SUS heated roll whose surface temperature was maintained at 75°C for about 2 seconds (drying shrinkage treatment). The shrinkage rate of the laminate in the width direction due to the drying shrinkage treatment was 2%. In this manner, a polarizer having a thickness of 7.4 μm was formed on the resin substrate.

[0154] 2. Preparation of Polarizing Plates A water-based polyurethane resin (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name: Superflex 210-R) was dissolved in a mixed solvent of pure water and isopropyl alcohol, and the resulting solution was applied to the surface of the polarizer formed on the resin substrate obtained above. Then, the solution was dried at 60°C to remove the solvent, and an easy-adhesion layer having a thickness of 0.15 μm was formed. 20 parts of an acrylic resin having a methyl methacrylate unit (manufactured by Kusumoto Chemical Industries, Ltd., product name: B728) was dissolved in 80 parts of methyl ethyl ketone to obtain an acrylic resin solution (20%). This acrylic resin solution was applied to the easy-adhesion layer using a wire bar, and the coating film was dried at 60°C for 5 minutes to form an acrylic resin layer constituted as a solidified product of the coating film. The acrylic resin layer had a thickness of 2 μm and a Tg of 116°C. Next, 70 parts by weight of dimethylol-tricyclodecane diacrylate (Kyoeisha Chemical, product name: Light Acrylate DCP-A), 20 parts by weight of isobornyl acrylate (Kyoeisha Chemical, product name: Light Acrylate IB-XA), 10 parts by weight of 1,9-nonanediol diacrylate (Kyoeisha Chemical, product name: Light Acrylate 1.9NA-A), and 3 parts by weight of a photopolymerization initiator (BASF, product name: Irgacure 907) were mixed in a solvent to obtain a coating liquid. The obtained coating liquid was applied onto the protective layer so that the thickness after curing was 3 μm. Next, the solvent was dried, and a high-pressure mercury lamp was used to apply an integrated light amount of 300 mJ / cm. 2The hard coat layer was formed by irradiating ultraviolet rays under a nitrogen atmosphere so that the thickness of the hard coat layer was 3 μm. Next, in order to stably perform the subsequent lamination work with the retardation layer, the adhesive layer of the polyethylene terephthalate (PET) film with an adhesive layer was laminated to the protective layer for reinforcement. After that, the resin substrate was peeled off to obtain a polarizing plate having a configuration of the PET film with an adhesive layer / protective layer (hard coat layer / acrylic resin layer (solidified product of the coating film)) / easy adhesion layer / polarizer.

[0155] 3. Preparation of the first alignment layer and the second alignment layer constituting the retardation layer A liquid crystal composition (coating liquid) was prepared by dissolving 10 g of a polymerizable liquid crystal exhibiting a nematic liquid crystal phase (manufactured by BASF: product name "Paliocolor LC242", represented by the following formula) and 3 g of a photopolymerization initiator for the polymerizable liquid crystal compound (manufactured by BASF: product name "Irgacure 907") in 40 g of toluene. [ka] The surface of a polyethylene terephthalate (PET) film (thickness 38 μm) was rubbed with a rubbing cloth and subjected to an alignment treatment. The direction of the alignment treatment was set to be 15° from the viewing side with respect to the direction of the absorption axis of the polarizer when it was attached to the polarizing plate. The above liquid crystal coating liquid was applied to this alignment-treated surface with a bar coater, and the liquid crystal compound was aligned by heating and drying at 90°C for 2 minutes. The liquid crystal layer thus formed was then irradiated with 100 mJ / cm using a metal halide lamp. 2 The liquid crystal layer was cured by irradiating the liquid crystal with light, thereby forming a liquid crystal alignment solidified layer A on the PET film. The liquid crystal alignment solidified layer A had a thickness of 2.5 μm and an in-plane retardation Re(550) of 270 nm. Furthermore, the liquid crystal alignment solidified layer A had a refractive index distribution of nx>ny=nz. A liquid crystal alignment layer B was formed on a PET film in the same manner as above, except that the coating thickness was changed and the alignment treatment direction was set to a 75° direction relative to the absorption axis direction of the polarizer when viewed from the viewing side. The liquid crystal alignment layer B had a thickness of 1.5 μm and an in-plane retardation Re(550) of 140 nm. Furthermore, the liquid crystal alignment layer B had a refractive index distribution of nx>ny=nz.

[0156] 4. Preparation of polarizing plate with retardation layer The liquid crystal alignment solidified layer A and the liquid crystal alignment solidified layer B obtained in the above 3 were transferred in this order onto the polarizer surface of the polarizing plate obtained in the above 2. At this time, the transfer (lamination) was performed so that the angle between the absorption axis of the polarizer and the slow axis of the alignment solidified layer A was 15°, and the angle between the absorption axis of the polarizer and the slow axis of the alignment solidified layer B was 75°. The transfer (lamination) was performed via the ultraviolet-curing adhesive (thickness 1.0 μm) used in the above 2. Next, the PET film with the adhesive layer was peeled off. In this way, a retardation layer-attached polarizing plate having a configuration of protective layer (hard coat layer / acrylic resin layer (solidified product of coating film)) / easy adhesion layer / polarizer / adhesive layer / retardation layer (first alignment solidified layer / adhesive layer / second alignment solidified layer) was obtained. The total thickness of the obtained retardation layer-attached polarizing plate was 19 μm.

[0157] [Examples 2 to 4] A polarizer having a thickness of 7.4 μm was formed on a resin substrate in the same manner as in Example 1, except that a dye bath having a different iodine concentration (weight ratio of iodine to potassium iodide=1:7) was used. Except for using the laminate having the polarizer / resin substrate structure obtained, a retardation layer-attached polarizing plate having a structure of protective layer (hard coat layer / acrylic resin layer (solidified coating film)) / easy adhesion layer / polarizer / adhesive layer / retardation layer (first alignment solidified layer / adhesive layer / second alignment solidified layer) was obtained in the same manner as in Example 1. The total thickness of the obtained retardation layer-attached polarizing plate was 19 μm.

[0158] [Examples 5 to 8] A polarizer having a thickness of 6.7 μm was formed on a resin substrate in the same manner as in Example 1, except that the stretching ratio in the underwater stretching treatment was 1.46 times, making the total stretching ratio 3.5 times, and that a dyeing bath having a different iodine concentration (weight ratio of iodine to potassium iodide = 1:7) was used. Except for using the laminate having the polarizer / resin substrate structure obtained, a retardation layer-attached polarizing plate having a structure of protective layer (hard coat layer / acrylic resin layer (solidified coating film)) / easy adhesion layer / polarizer / adhesive layer / retardation layer (first alignment solidified layer / adhesive layer / second alignment solidified layer) was obtained in the same manner as in Example 1. The total thickness of the obtained retardation layer-attached polarizing plate was 18 μm.

[0159] [Example 9] A polarizing plate with a retardation layer was obtained in the same manner as in Example 7, except that an acrylic resin having a lactone ring unit, which was polymethyl methacrylate (lactone ring unit: 30 mol%), was used instead of an acrylic resin having a methyl methacrylate unit (manufactured by Kusumoto Chemical Industries, Ltd., product name: B728). The total thickness of the obtained polarizing plate with a retardation layer was 18 μm.

[0160] [Example 10] A polarizing plate with a retardation layer was obtained in the same manner as in Example 9, except that an acrylic resin having a glutarimide ring unit (4 mol% of glutarimide ring unit) that is polymethyl methacrylate was used instead of an acrylic resin having a methyl methacrylate unit (Kusumoto Chemical Industries, Ltd., product name: B728). The total thickness of the obtained polarizing plate with a retardation layer was 18 μm.

[0161] [Example 11] In Example 9, instead of the acrylic resin solution, 20 parts of an epoxy resin (manufactured by Mitsubishi Chemical Corporation, product name: jER (registered trademark) YX6954BH30, weight average molecular weight: 36000, epoxy equivalent: 13000) was dissolved in 80 parts of methyl ethyl ketone to form a protective layer constituted as a solidified coating film using an epoxy resin solution (20%). Specifically, this epoxy resin solution was applied to the easy-adhesion layer using a wire bar, and the coating film was dried at 60 ° C for 3 minutes to form a protective layer. The thickness of the protective layer was 3 μm, and Tg was 130 ° C. In this way, a retardation layer-attached polarizing plate 7 was obtained in the same manner as in Example 9, except that a protective layer was formed, an easy-adhesion layer was not formed on the polarizer, and a hard coat layer was not formed. The total thickness of the obtained retardation layer-attached polarizing plate was 16 μm.

[0162] [Example 12] A polarizing plate with a retardation layer was obtained in the same manner as in Example 7, except that a protective layer was formed as follows, an easy-adhesion layer was not formed on the polarizer, and a hard coat layer was not formed. The total thickness of the obtained polarizing plate with a retardation layer was 16 μm. 15 parts of an epoxy resin having a biphenyl skeleton (manufactured by Mitsubishi Chemical Corporation, product name: jER (registered trademark) YX4000) was dissolved in 83.8 parts of methyl ethyl ketone to obtain an epoxy resin solution. 1.2 parts of a photocationic polymerization initiator (manufactured by San-Apro Co., Ltd., product name: CPI (registered trademark)-100P) was added to the obtained epoxy resin solution to obtain a protective layer forming composition. The obtained protective layer forming composition was applied to the easy-adhesion layer using a wire bar, and the applied film was dried at 60°C for 3 minutes. Next, a high-pressure mercury lamp was used to obtain an integrated light amount of 600 mJ / cm. 2 The protective layer was formed by irradiating the film with ultraviolet light so that the thickness of the protective layer was 3 μm.

[0163] [Example 13] A polarizing plate with a retardation layer was obtained in the same manner as in Example 12, except that a bisphenol-type epoxy resin (manufactured by Mitsubishi Chemical Corporation, product name: jER (registered trademark) 828) was used instead of the epoxy resin having a biphenyl skeleton. The total thickness of the obtained polarizing plate with a retardation layer was 16 μm.

[0164] [Example 14] A polarizing plate with a retardation layer was obtained in the same manner as in Example 12, except that a hydrogenated bisphenol type epoxy resin (manufactured by Mitsubishi Chemical Corporation, product name: jER (registered trademark) YX8000) was used instead of the epoxy resin having a biphenyl skeleton. The total thickness of the obtained polarizing plate with a retardation layer was 16 μm.

[0165] [Example 15] 15 parts of hydrogenated bisphenol type epoxy resin (manufactured by Mitsubishi Chemical Corporation, product name: jER (registered trademark) YX8000) and 10 parts by weight of oxetane resin (manufactured by Toagosei Co., Ltd., product name: Aron Oxetane (registered trademark) OXT-221) were dissolved in 73 parts of methyl ethyl ketone to obtain an epoxy resin solution. 2 parts of a photocationic polymerization initiator (manufactured by San-Apro Co., Ltd., product name: CPI (registered trademark)-100P) were added to the obtained epoxy resin solution to obtain a protective layer forming composition. A retardation layer-attached polarizing plate was obtained in the same manner as in Example 12 except that the obtained protective layer-forming composition was used. The total thickness of the obtained retardation layer-attached polarizing plate was 16 μm.

[0166] [Example 16] A polarizing plate with a retardation layer was obtained in the same manner as in Example 15, except that the thickness of the protective layer was changed to 8 μm.

[0167] [Example 17] A polarizing plate with a retardation layer was obtained in the same manner as in Example 15, except that the thickness of the protective layer was set to 10 μm.

[0168] [Example 18] A protective layer (cured product) was formed in the same manner as in Example 12, except that an ultraviolet-curable epoxy resin (manufactured by Daicel Corporation, product name "Celloxide 2021P") was used. Specifically, a composition containing 95% by weight of the epoxy resin and 5% by weight of a photopolymerization initiator (CPI-100P, manufactured by San-Apro Co., Ltd.) was applied onto the easy-adhesion layer, and a high-pressure mercury lamp was used in an air atmosphere to irradiate the protective layer with an accumulated light amount of 500 mJ / cm. 2 The film was irradiated with ultraviolet light at 1000 nm to form a hardened layer (protective layer). A polarizing plate with a retardation layer was produced in the same manner as in Example 7, except that this protective layer was used. The polarizing plate had a thickness of 16 μm.

[0169] [Examples 19 to 22] A polarizer having a thickness of 6.2 μm was formed on a resin substrate in the same manner as in Example 1, except that the underwater stretching ratio was 1.67 times (resulting in a total stretching ratio of 4.0 times) and a dye bath having a different iodine concentration (weight ratio of iodine to potassium iodide=1:7) was used. Except for using the laminate having the polarizer / resin substrate structure obtained, a retardation layer-attached polarizing plate having a structure of protective layer (hard coat layer / acrylic resin layer (solidified coating film)) / easy adhesion layer / polarizer / adhesive layer / retardation layer (first alignment solidified layer / adhesive layer / second alignment solidified layer) was obtained in the same manner as in Example 1. The total thickness of the obtained retardation layer-attached polarizing plate was 18 μm.

[0170] [Examples 23 to 26] A polarizer having a thickness of 6.0 μm was formed on a resin substrate in the same manner as in Example 1, except that the underwater stretching ratio was set to 1.88 times, the total stretching ratio was set to 4.5 times, and a dye bath having a different iodine concentration (weight ratio of iodine to potassium iodide=1:7) was used. Except for using the laminate having the polarizer / resin substrate structure obtained, a retardation layer-attached polarizing plate having a structure of protective layer (hard coat layer / acrylic resin layer (solidified coating film)) / easy adhesion layer / polarizer / adhesive layer / retardation layer (first alignment solidified layer / adhesive layer / second alignment solidified layer) was obtained in the same manner as in Example 1. The total thickness of the retardation layer-attached polarizing plate obtained was 17.0 μm.

[0171] (Comparative Examples 1 to 4) A polarizer having a thickness of 5.5 μm was formed on a resin substrate in the same manner as in Example 1, except that the underwater stretching ratio was set to 2.29 times, the total stretching ratio was set to 5.5 times, and a dye bath having a different iodine concentration (weight ratio of iodine to potassium iodide=1:7) was used. Except for using the laminate having the polarizer / resin substrate structure obtained, a retardation layer-attached polarizing plate having a structure of protective layer (hard coat layer / acrylic resin layer (solidified coating film)) / easy adhesion layer / polarizer / adhesive layer / retardation layer (first alignment solidified layer / adhesive layer / second alignment solidified layer) was obtained in the same manner as in Example 1. The total thickness of the retardation layer-attached polarizing plate obtained was 16 μm.

[0172] Comparative Example 5 A polarizer having a thickness of 5.5 μm was obtained in the same manner as in Example 1, except that the stretching ratio in the underwater stretching treatment was 2.29 times, the total stretching ratio was 5.5 times, and the liquid temperature of the stretching bath was 70° C. A polarizer having a thickness of 5.5 μm was obtained in the same manner as in Example 1, except that an acrylic resin film having a thickness of 40 μm was laminated on the surface of the obtained polarizer via an ultraviolet-curable adhesive to form a protective layer. A polarizing plate with a retardation layer was obtained in the same manner as in Example 1. The total thickness of the obtained polarizing plate with a retardation layer was 53 μm.

[0173] Comparative Example 6 Except for using an acrylic film having a thickness of 20 μm as the protective layer, a polarizing plate with a retardation layer was obtained in the same manner as in Comparative Example 2. The total thickness of the obtained polarizing plate with a retardation layer was 33 μm.

[0174] Comparative Example 7 A polarizing plate with a retardation layer was obtained in the same manner as in Comparative Example 2, except that a protective layer was formed in the same manner as in Example 11. The total thickness of the obtained polarizing plate with a retardation layer was 15 μm.

[0175] Comparative Example 8 A polarizing plate with a retardation layer was obtained in the same manner as in Comparative Example 2, except that a protective layer was formed in the same manner as in Example 12. The total thickness of the obtained polarizing plate with a retardation layer was 15 μm.

[0176] Comparative Example 9 A polarizing plate with a retardation layer was obtained in the same manner as in Comparative Example 2, except that a protective layer was formed in the same manner as in Example 15. The total thickness of the obtained polarizing plate with a retardation layer was 15 μm.

[0177] [evaluation] The retardation layer-attached polarizing plates obtained in the Examples and Comparative Examples were subjected to the following evaluations. The results are shown in Table 1. (1) Thickness The thickness of the polarizer was measured using an interference thickness meter (Otsuka Electronics Co., Ltd., product name "MCPD-3000"). The calculated wavelength range used for thickness calculation was 400 nm to 500 nm, and the refractive index was 1.53. The thickness of the protective layer was measured using an interference thickness meter (Otsuka Electronics Co., Ltd., product name "MCPD-3000"), with the calculated wavelength range and refractive index appropriately selected. The thickness of the easy-adhesion layer was obtained by observation with a scanning electron microscope (SEM). Thicknesses exceeding 110 μm were measured using a digital micrometer (Anritsu Co., Ltd., product name "KC-351C"). (2) In-plane retardation of PVA (Re) For the polarizer (single polarizer) obtained by peeling and removing the resin substrate from the laminate of polarizer / thermoplastic resin substrate obtained in the examples and comparative examples, the in-plane retardation (Rpva) of PVA at a wavelength of 1000 nm was evaluated using a retardation measurement device (manufactured by Oji Scientific Instruments, product name "KOBRA-31X100 / IR") (this is the value obtained by subtracting the in-plane retardation (Ri) of iodine from the total in-plane retardation at a wavelength of 1000 nm according to the principle explained above). The absorption edge wavelength was set to 600 nm. (3) Birefringence of PVA (Δn) The birefringence (Δn) of the PVA was calculated by dividing the in-plane retardation of the PVA measured in (2) above by the thickness of the polarizer. (4) Orientation function For the polarizers used in the examples and comparative examples, a Fourier transform infrared spectrophotometer (FT-IR) (manufactured by Perkin Elmer, product name: "Frontier") was used to measure attenuated total reflection (ATR) spectroscopy of the polarizer surface using polarized infrared light as the measurement light. Germanium was used as the crystallite to which the polarizer was attached, and the angle of incidence of the measurement light was 45°. The orientation function was calculated using the following procedure. The polarized infrared light (measurement light) to be incident was polarized light (s-polarized light) that vibrated parallel to the surface to which the germanium crystal sample was attached, and the absorbance spectrum of each was measured with the stretch direction of the polarizer positioned perpendicular (⊥) and parallel ( / / ) to the polarization direction of the measurement light. From the obtained absorbance spectrum, the (3330 cm -1 Intensity) was used as a reference (2941 cm -1 The intensity I was calculated. ⊥ is obtained from the absorbance spectrum obtained when the stretching direction of the polarizer is arranged perpendicular (⊥) to the polarization direction of the measurement light (2941 cm -1 strength) / (3330cm -1 In addition, I / / is obtained from the absorbance spectrum obtained when the stretching direction of the polarizer is arranged parallel ( / / ) to the polarization direction of the measurement light (2941 cm -1 strength) / (3330cm -1 Intensity), where (2941 cm -1 Intensity) is the bottom of the absorbance spectrum, 2770 cm -1 and 2990cm -1 2941cm when using this as the baseline -1 is the absorbance of (3330cm -1 Strength) is 2990cm -1 and 3650cm -1 3330cm when the baseline is -1 The absorbance of the obtained I ⊥ and I / / The orientation function f was calculated according to formula 1. Note that f = 1 is perfect orientation, and f = 0 is random. -1The peak at 3330cm is said to be due to the vibration of the main chain (-CH2-) of PVA in the polarizer. -1 The peak is said to be due to the vibration of the hydroxyl group of PVA. (Formula 1)f=(3 <cos 2 θ>-1) / 2 =(1-D) / [c(2D+1)] however c = (3cos 2 β-1) / 2 So, as mentioned above, 2941cm -1 When using, β=90°⇒f=-2×(1-D) / (2D+1). θ: Angle of molecular chain to stretching direction β: Angle of the transition dipole moment with respect to the chain axis D=(I ⊥ ) / (I / / ) I ⊥ : Absorption intensity when the polarization direction of the measurement light and the stretching direction of the polarizer are perpendicular I / / : Absorption intensity when the polarization direction of the measurement light and the stretching direction of the polarizer are parallel (5) Crack occurrence rate The retardation layer-attached polarizing plates obtained in the examples and comparative examples were cut into a size of 10 mm x 10 mm. The cut retardation layer-attached polarizing plates were attached to a glass plate (thickness 1.1 mm) via an acrylic adhesive layer having a thickness of 20 μm. The sample attached to the glass plate was placed in an oven at 100 degrees for 120 hours, and then visually confirmed whether or not cracks occurred in the absorption axis direction (MD direction) of the polarizer. This evaluation was performed using three retardation layer-attached polarizing plates, and the number of retardation layer-attached polarizing plates in which cracks occurred was evaluated. (6) Bending resistance The retardation layer-attached polarizing plate obtained in the examples and comparative examples was cut into a size of 50 mm x 100 mm. At this time, the polarizing plate was cut out so that the absorption axis direction of the polarizer was the long side direction. Using a bending tester (manufactured by Yuasa Systems Co., Ltd., product name: DLDM111LH), the cut retardation layer-attached polarizing plate was subjected to a bending test at room temperature. Specifically, the retardation layer-attached polarizing plate was bent 50,000 times in the absorption axis direction with the retardation layer side on the inside and the protective layer or the hard coat layer formed on the protective layer on the outside, at a rotation speed of 60 rpm, with a bending diameter set to 1 mmφ (R is 0.5 mm). Next, the retardation layer-attached polarizing plate after the test was visually checked for the presence or absence of cracks, and those in which no cracks were found were rated as good, and those in which cracks were found were rated as bad. The bending direction was the transmission axis direction of the polarizer. (7) Single unit transmittance and polarization degree For the polarizers used in the examples and comparative examples, the single transmittance Ts, parallel transmittance Tp, and crossed transmittance Tc were measured using an ultraviolet-visible spectrophotometer (manufactured by JASCO Corporation, product name "V-7100") and were designated as Ts, Tp, and Tc of the polarizer, respectively. These Ts, Tp, and Tc are Y values ​​measured using a 2-degree visual field (C light source) according to JIS Z8701 and corrected for visibility. From the obtained Tp and Tc, the degree of polarization P was calculated according to the following formula. Polarization degree P(%)={(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100 (8) Puncture strength The polarizer was peeled off from the laminate of polarizer / thermoplastic resin substrate used in the examples and comparative examples, and placed on a compression tester (manufactured by Kato Tech, product name "NDG5" needle penetration force measurement specifications) equipped with a needle, and pierced at a piercing speed of 0.33 cm / sec under a room temperature (23°C ± 3°C) environment. The strength at which the polarizer broke was taken as the breaking strength (piercing strength). The evaluation value was the average value of the breaking strengths of 10 sample pieces. The needle used had a tip diameter of 1 mmφ and 0.5R. The polarizer to be measured was fixed by clamping it from both sides with a jig having a circular opening with a diameter of about 11 mm, and the needle was pierced into the center of the opening to perform the test.

[0178] [Table 1]

[0179] As is clear from Table 1, the retardation layer-attached polarizing plates of Examples 1 to 26 were prevented from cracking even when subjected to heat treatment. In addition, they were also excellent in durability when folded. [Industrial Applicability]

[0180] The retardation layer-attached polarizing plate of the present invention is suitably used in an image display device. [Explanation of symbols]

[0181] 10 Polarizing plate 11 Polarizer 12 First protective layer 13 Second layer of protection 20 Retardation layer 100 Polarizing plate with retardation layer 101 Polarizing plate with retardation layer 102 Polarizing plate with retardation layer

Claims

1. A polarizing plate including a polarizer formed of a polyvinyl alcohol-based resin film containing a dichroic material and a protective layer disposed on one side of the polarizer, and a retardation layer; The thickness of the polarizer is 10 μm or less, The piercing strength of the polarizer is 30 gf / μm or more, the retardation layer is a layer in which a liquid crystal compound is aligned and solidified, The thickness of the protective layer is 10 μm or less, the protective layer is made of at least one selected from the group consisting of a solidified coating film of a solution of a thermoplastic (meth)acrylic resin in an organic solvent, a photocationically cured product of an epoxy resin, and a solidified coating film of a solution of an epoxy resin in an organic solvent, When the single transmittance of the polarizer is x % and the birefringence, which is the in-plane retardation of the polyvinyl alcohol-based resin at 23° C. and a wavelength of 1000 nm divided by the thickness of the polarizer, is y, the polarizer satisfies the following formula (1): A polarizing plate with a retardation layer, the total thickness of which is 30 μm or less. y<-0.011x+0.525 (1)

2. A polarizing plate including a polarizer formed of a polyvinyl alcohol-based resin film containing a dichroic material and a protective layer disposed on one side of the polarizer, and a retardation layer; The thickness of the polarizer is 10 μm or less, The piercing strength of the polarizer is 30 gf / μm or more, the retardation layer is a layer in which a liquid crystal compound is aligned and solidified, The thickness of the protective layer is 10 μm or less, the protective layer is made of at least one selected from the group consisting of a solidified coating film of a solution of a thermoplastic (meth)acrylic resin in an organic solvent, a photocationically cured product of an epoxy resin, and a solidified coating film of a solution of an epoxy resin in an organic solvent, When the single transmittance of the polarizer is x % and the in-plane retardation of the polyvinyl alcohol-based resin film at 23° C. and a wavelength of 1,000 nm is z nm, the polarizer satisfies the following formula (2): A polarizing plate with a retardation layer, the total thickness of which is 30 μm or less. z<-60x+2875 (2)

3. A polarizing plate including a polarizer formed of a polyvinyl alcohol-based resin film containing a dichroic material and a protective layer disposed on one side of the polarizer, and a retardation layer; The thickness of the polarizer is 10 μm or less, The piercing strength of the polarizer is 30 gf / μm or more, the retardation layer is a layer in which a liquid crystal compound is aligned and solidified, The thickness of the protective layer is 10 μm or less, the protective layer is made of at least one selected from the group consisting of a solidified coating film of a solution of a thermoplastic (meth)acrylic resin in an organic solvent, a photocationically cured product of an epoxy resin, and a solidified coating film of a solution of an epoxy resin in an organic solvent, When the single transmittance of the polarizer is x % and the orientation function of the polyvinyl alcohol-based resin is f, the polarizer satisfies the following formula (3): A polarizing plate with a retardation layer having a total thickness of 30 μm or less: f<-0.018x+1.11 (3) Here, the orientation function of the polyvinyl alcohol resin is a value determined by attenuated total reflection spectroscopy using a Fourier transform infrared spectrophotometer and polarized light as measuring light.

4. 4. The retardation layer-attached polarizing plate according to claim 1, wherein the polarizer has a single transmittance of 40.0% or more and a polarization degree of 99.0% or more.

5. 5. The polarizing plate with a retardation layer according to claim 1, wherein the thermoplastic (meth)acrylic resin has at least one repeating unit selected from the group consisting of a lactone ring unit, a glutaric anhydride unit, a glutarimide unit, a maleic anhydride unit and a maleimide unit.

6. 5. The polarizing plate with a retardation layer according to claim 1, wherein the protective layer is a photocationically cured product of an epoxy resin having at least one selected from the group consisting of an aromatic skeleton and a hydrogenated aromatic skeleton.

7. An image display device comprising the retardation layer-attached polarizing plate according to claim 1 .

Citation Information

Patent Citations

  • Assembling of shield drilling machine

    JP1983011296A

  • Polarizing plate and method for manufacturing the same

    JP2001343521A

  • Manufacturing methods for stretched film and polarizing film

    JP2017187731A

  • Film laminate for touch panel

    JP2018116543A

  • Battery system

    JP2019003954A